Enzymatic Construction Materials for Repair and Corrosion Resistance and Durability

JP2025506697APending Publication Date: 2025-03-13WORCESTER POLYTECHNIC INSTITUTE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024548554
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-17
Filing Date
2023-02-16
Publication Date
2025-03-13

Smart Images

  • Figure 2025506697000001_ABST
    Figure 2025506697000001_ABST
Patent Text Reader

Abstract

Methods are provided for repairing cracks and pits in concrete using carbonic anhydrase embedded in gelatin, hydrogel or other aqueous matrix. Durable corrosion resistant concrete mixtures containing carbonic anhydrase are provided, and methods for making and using durable corrosion resistant concrete are provided. Corrosion resistance and durability come from reduced porosity compared to concrete without the enzyme, reducing access of harmful materials such as chloride ions to the interior of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Technical Field Methods for making cementitious construction materials with increased durability and corrosion resistance, as well as methods for repairing defects in cement, are provided. [Background technology]

[0002] background Concrete is a valuable building material due to its compressive strength and resistance to atmospheric elements. Concrete is a general term applied to a mixture of Portland cement and aggregates, typically sand and various sizes of gravel. The Portland cement reacts with water to bind the aggregates and hardens to form a solid mass. Concrete is easily transported as a dry material with the texture of powdery gravel, and forms a flowable, gritty, slurry-like material immediately when mixed with water. Before hardening, the flowable mixture can be cast or poured into any suitable shape, and after about 90 minutes of mixing with water, it begins to harden into the desired shape and exhibits significant compressive strength and mass.

[0003] Excluding water, concrete is the most consumed material on earth, with 3 tonnes used per person per year. Carbon dioxide emissions from waste concrete and cement production and transportation from construction are increasing every year, with concrete alone accounting for 9% of total CO2 emissions. Average temperatures in the Arctic are rising faster than anywhere else on Earth, due to sea level rise caused by the greenhouse effect. Climate change caused by rising CO2 levels due to human activities is the greatest real threat facing the world. It is therefore urgent to reduce carbon dioxide emissions and mitigate the greenhouse effect. The use of large amounts of pozzolanic substitutes such as fly ash and slag in concrete consumption is an environmentally unfriendly method of reducing concrete consumption.

[0004] Concrete, in its various forms, is one of the most widely used construction materials worldwide. The cumulative deterioration of concrete is caused by salts, alkalis, freeze-thaw cycles, carbonation and physical wear. The commonly used repair materials for concrete cracks mainly include epoxy-based and acrylic resins, which are all not environmentally friendly and often cause delamination or cracks between the original concrete matrix and the repair material.

[0005] Repair processes for cracked and damaged concrete typically rely on the combination of dissimilar materials such as inorganic calcium-silica-hydrate (CSH) compositions and organic petroleum-derived epoxies. However, patching and resurfacing is highly dependent on the skills of the artisan and often causes further damage, thereby hindering the repair process. Summary of the Invention [Problem to be solved by the invention]

[0006] Considering the enormous volume and worldwide nature of the deterioration and corrosion of concrete in roads, bridges and buildings, there is an urgent need for materials and methods for repairing cracks and fissures in cementitious surfaces that are environmentally friendly and do not cause further damage, as well as methods for producing durable concrete that is resistant to corrosion, and concrete mixtures for construction materials characterized by high resistance to environmental degradation. [Means for solving the problem]

[0007] overview One aspect of the invention herein is a method of repairing at least one crack or pit in a cementitious surface, comprising: treating at least one crack or pit in the cementitious surface with at least one carbonic anhydrase preparation, the preparation containing carbonic anhydrase non-covalently immobilized on a granular substrate or embedded in a semi-solid bead matrix; subjecting the cementitious treated surface to ambient conditions of atmospheric carbon dioxide and temperature, thereby repairing the cracks; One embodiment of the method further comprises repeating the treatment of the at least one crack or pit with the carbonic anhydrase preparation and subjecting the treated surface to ambient conditions. To repeat the treatment step, the method further comprises air drying the treated cementitious surface before repeating the treatment.

[0008] In various alternative embodiments, the carbonic anhydrase preparation further comprises at least one additional component selected from natural carbonic anhydrase, calcium ions, a buffer, and water. Natural carbonic anhydrase has an amino acid sequence found in nature, and the enzyme is found throughout the range of biological organisms, both prokaryotes and eukaryotes, so that the enzyme suitable for the methods and materials described herein can be obtained from any source. In various alternative embodiments, the granular substrate of the carbonic anhydrase preparation is one or more of silicone beads, silicon dioxide, silica gel, disiloxane, silicic acid, silanol, organosilicon compounds, sand, grit, cellulose, and cellulose derivatives. In various embodiments, the semi-solid bead matrix of the carbonic anhydrase preparation is prepared from at least one selected from hydrogel, agar, and gelatin.

[0009] In one embodiment of the method, the CA is recombinantly produced. Alternatively, the CA is purified or partially purified from food industry by-products or fermentation by-products. Carbonic anhydrase is recombinantly produced or prepared directly from natural biological sources, since widespread use of this enzyme requires a large supply, and the source is determined by economic factors. Carbonic anhydrase is found in organisms ranging from bacteria to mammals. Economical and convenient sources of carbonic anhydrase are, for example, waste products from the meat industry, such as bovine blood, waste products from beer production, and other microbial fermentations where cellular material is discarded.

[0010] Carbonic anhydrase in various embodiments is purified or semi-purified or crudely extracted, for example produced from crude lysates of cells by organic solvent extraction or a few rounds of ammonium sulfate precipitation. Thus, in various alternative embodiments, carbonic anhydrase is purified or partially purified from biological sources, for example, a mammalian enzyme by-product of the meat industry, for example produced from bovine blood, or a bacterial or yeast enzyme by-product of antibiotic or high value protein fermentation. Particular applications of the method may involve obtaining carbonic anhydrase from bacterial species that are thermophilic or xerophilic species. Recombinant carbonic anhydrase may be produced by expression of a gene encoding the enzyme, for example expressed in E. coli, Streptomyces lividans, or Saccharomyces cerevisiae, and secreted into the fermentation medium.

[0011] Another aspect of the invention herein provides a method for improving durability and corrosion resistance of a cementitious surface, the method comprising: contacting the pre-hardened cement mixture with at least one carbonic anhydrase (CA) preparation to form an enzyme-cement mixture (ECM); applying an ECM to the surface and subjecting the ECM on the surface to ambient atmosphere to harden, thereby improving durability and corrosion resistance by reducing the porosity of the resulting CA-contacted cementitious surface compared to a control cement not contacted with CA. Includes.

[0012] The method uses a carbonic anhydrase preparation with the enzyme embedded or non-covalently immobilized on a granular substrate selected from silicone beads, silica gel, sand, grit, cellulose, cellulose derivatives, or the carbonic anhydrase preparation includes CA embedded in a semi-solid bead matrix including hydrogel or gelatin. The embedding, or immobilization, or attachment of CA results in better distribution in the cementitious mixture compared to CA solutions. Although gelatin has a low transition temperature from solid or semi-solid to liquid, the association of the enzyme with gelatin in liquid form is also beneficial for the distribution of the enzyme in the resulting cementitious product. Matrix materials with high melting points such as agar can be used in preparations with low percentages of agar, for example, less than 1% or 2%, and agar / gelatin mixtures are also envisioned.

[0013] The ECM materials and methods of forming ECM herein provide a resulting CA-contacted cementitious surface with reduced permeability to harmful environmental corrosive agents. The reduced porosity is brought about by calcareous crystallization shown herein to result from the action of carbonic anhydrase. An important consequence of reducing the porosity of the resulting cementitious surface is reduced permeability by harmful salt ions, including chloride salts. Corrosion by chloride ions of steel rebar in reinforced concrete used in construction is thereby prevented or reduced.

[0014] In various embodiments of the methods herein, the contacting step comprises contacting with Ca ++ The method further includes adding environmental Ca ions to the ECM. ++ In situations where Ca is sufficient, ++ This is done without the addition of calcium, because calcium is the fifth most abundant element in the Earth's crust. ++ The step of adding ions accelerates the resulting porosity reduction process. As an alternative to adding calcium to the ECM, the applying step can be performed after the contacting step, e.g., before or after curing. ++ This involves applying ions to the surface. For example, Ca ++ is a solution of calcium formate.

[0015] One aspect of the invention herein provides a cement substitute known as an ECM having improved durability and corrosion resistance, wherein the cement mixture comprises carbonic anhydrase in an aqueous solution, the enzyme is attached or embedded or enmeshed in a particulate admixture, the enzyme is associated with at least one matrix selected from gelatin, agar or hydrogel, or is associated with at least one particulate material selected from silicone beads, silica gel, sand, grit, cellulose and cellulose derivatives at a pH of 4.5 to 9.5.

[0016] In various alternative embodiments, the corrosion resistant cement mixture contains an enzyme at a concentration in a range selected from the group consisting of 100 nM to 500 nM, 500 nM to 1 μM, 1 μM to 5 μM, and 5 μM to 10 μM. One embodiment of the cement mixture includes Ca ++ Further includes:

[0017] In gelatin-containing cementitious mixtures, the compositions described herein and methods of making and using these compositions provide corrosion-resistant and durable concrete and methods of repairing cracks in concrete. Additional examples can be found in Matter 5: 1-18 published March 2, 2022, authors Wang, Shuai, Scarlata, Suzanne F. and Rahbar, Nima, which is incorporated herein by reference in its entirety. [Brief description of the drawings]

[0018] BRIEF DESCRIPTION OF THE DRAWINGS [Figure 1] FIG. 1 is a schematic diagram showing the preparation and manufacturing of enzymatic construction materials (ECMs) and the enzymatic repair process. [Diagram 2]FIG. 1 is a graph showing weight gain for four different material designs with constant CO2 gassing at a rate of 5 bubbles / sec. The addition of base enhances the weight gain, with the weight gain being highest for the ECa sample. In the box plot, the median is indicated by (-), the mean is indicated by (□), the values ​​at 25% and 75% are shown as the edges of the box, and the values ​​at the 5% and 95% levels are shown as whiskers. The weight gain is observed to be due to fixation of CO2 by the action of carbonic anhydrase. [Diagram 3] FIG. 1 is a series of micrographs showing scanning electron microscope (SEM) images and energy dispersive spectroscopy (EDS) maps comparing the effect of CA enzyme as an aqueous additive, calcium source, and high pH on different samples. CA enzyme catalysis results in an ECM with an organized structure. Calcium is evenly distributed on the ECM surface and crosslinks. Compared to the control GL (gelatin), GCa (gelatin + Ca2+) and BGE (base + gelatin + CA + Ca2+) samples, the mineral crosslinks in the ECM have wider and longer dimensions. The EDS map of the ECM sample also shows the highest amount of calcite crystals compared to the other three samples. The calcite crosslinks distributed throughout the ECM and the organized structure result in greater strength, durability, and lower porosity. [Figure 4A] 1 is a micrograph showing that the dimensions of typical crystalline bridges in the "non-gelatin" sample ECa are smaller than typical bridges in ECM. These data are evidence that gelatin can establish a suitable skeletal framework for crystal formation, further enhancing and expanding the size of the crystalline bridges. [Figure 4B] 1 is a micrograph showing that the dimensions of typical crystalline bridges in the "non-gelatin" sample ECa are smaller than typical bridges in ECM. These data are evidence that gelatin can establish a suitable skeletal framework for crystal formation, further enhancing and expanding the size of the crystalline bridges. [Figure 4C]1 is a photomicrograph showing a typical crack initiating and propagating at the calcite bridges that bind the sand particles. Provided herein is a method for repairing cracks and fissures in existing concrete, utilizing the properties of enzymes in gelatin. [Figure 4D] 1 is a photomicrograph showing a typical crack initiating and propagating at the calcite bridges that bind the sand particles. Provided herein is a method for repairing cracks and fissures in existing concrete, utilizing the properties of enzymes in gelatin. [Figure 4E] 1 is a micrograph showing the detachment of sand particles from the matrix. [Figure 4F] 1 is a micrograph showing the detachment of sand particles from the matrix. [Figure 5A] This is a photograph of a CA sand slurry sample prepared with white sand of No. 50 (sand retained on a 300 m sieve). [Figure 5B] Photographs of CA sand slurry samples after uniaxial compression tests. [Figure 5C] Photographs of CA sand slurry samples prepared with No. 30 coarse sand (retained on the 600 m sieve). [Figure 5D] FIG. 1 is a graph showing the compressive strength of fine sand slurry samples prepared with five different aqueous solutions. It is observed that ECM exhibits the highest compressive strength (9 MPa). [Figure 5E] 1 is a graph showing the tangent modulus of fine sand slurry samples prepared with five different aqueous solutions. It is observed that ECM exhibits the highest tangent modulus. [Figure 6A] This is a photograph of a single-sided dent bending (SENB) test. [Figure 6B] 1 is a graph showing the fracture energy of three different groups of sand slurry beam samples: GL, GCa and ECM. The results show that the ECM sample has the highest fracture energy, resulting in a more durable product. [Figure 6C]1 is a graph showing the load-displacement curves of three different groups of sand slurry beam samples: GL, GCa and ECM. The results show that the ECM samples have the highest ultimate load, resulting in a more durable product. [Figure 7] FIG. 1 is a series of micrographs showing optical (top) and SEM (bottom) images of the enzyme-catalyzed mineral precipitation and growth process in a sand-gelatin system during the first 20 minutes of hardening. [Figure 8] FIG. 1 is a graph showing the time-dependent mineral thickness ratio (H=R) as a function of time. H is the thickness of the mineral bridges and R is the average thickness of the gelatin network in the sand-gelatin system. The solid line represents the numerical results from the diffusion model and the dots represent the data. [Figure 9A] Photograph of the single-sided recessed ECM beam sample before destructive testing. [Figure 9B] Photograph of the one-sided recessed ECM beam sample after destructive testing. [Figure 9C] Photograph showing that the fractured sample was placed in a silicon mold and treated along the crack area with (3 parts) calcium-enzyme solution and CO2 gas. [Figure 9D] This is a photograph showing that the cracks have been repaired after treatment. [Figure 9E] 13 is a series of photographs showing repaired samples after drying with calcium carbonate crystals visible in the fractured areas. [Figure 9F] The specimens were reconditioned after each cycle and the ultimate failure load is reported after every 6 cycles. [Figure 10] Schematic of the self-repair mechanism in which, after disruption, application of CO2 allows the enzyme catalysis of CA to rebuild the broken mineral cross-links with calcium, re-establishing the cross-linked network that holds the material's microstructure together. [Figure 11] FIG. 1 is a graph of the compressive strength of ECM (n=14), glutaraldehyde-modified ECM (n=7), and tannin-modified ECM (n=5). The glutaraldehyde-modified ECM samples exhibit an impressive average strength of 12 MPa. [Figure 12] Powder X-ray diffraction (pXRD) analysis of the crystals produced by the CA enzymatic method compared to a reference spectrum of calcite. This comparison confirms that the product crystallinity from the enzymatic method is calcite. [Figure 13] FIG. 11 is a series of graphs showing Fourier transform infrared spectroscopy (FT-IR) analysis of enzyme-generated Ca-carbonate and comparing it with a reference spectrum where the sample precipitate had a dry weight of 0.4 μg, confirming the chemical composition of the remediated product resulting from the enzyme solution. [Figure 14A] 1 is a photograph of a coarse sand slurry cube. [Figure 14B] 1 is a graph showing the compressive strength of coarse sand slurry cubes with CA enzyme catalysis (gelatin + Ca2++CA) compared to the intact control. The sample shows the highest average compressive strength of 4.2 MPa. [Figure 15A] 13 is a photograph showing a destructive test on a coarse sand slurry beam. [Figure 15B] 1 is a graph showing a destructive test on a coarse sand slurry beam. [Figure 15C] 1 is a graph showing the results of a coarse sand beam bending test. [Figure 16] FIG. 1 is a series of photomicrographs showing optical microscopy images (top) and SEM images (bottom) of mineral precipitation and growth in a typical ECM sample within 10 minutes. [Figure 17A] 1 is a graph showing calcium concentration as a function of crosslink radius. [Figure 17B] 1 is a graph showing a linear approximation of a concentration profile. [Figure 18] FIG. 1 is a schematic diagram showing the preparation and fabrication of enzyme construction material-n (ECM-n), the enzyme repair process and the use of laser for curing. [Figure 19A] Photograph showing the experimental setup for laser-induced ECM-n hardening. [Figure 19B] Thermal images showing the top view of the temperature change in ECM-n. The maximum temperature increases to 81.5°C in 60 min (n=5, Med=81.5, SD=3). [Figure 19C] FIG. 11 is a thermal image showing a profile of temperature contours in ECM-n. [Figure 19D] Graph showing temperature as a function of cure time at the center of a 12.5 mm cube sample surface of 0.1% nanoparticle-modified ECM-n under 3 W laser induction compared to ECM without nanoparticles. Data for ECM and ECM-n were obtained from a median group of 5 independent samples (n=5). [Figure 20] 1 is a graph showing normalized heat flow for initial curing of ECM-n at 25° C. and 60° C. FIG. 2 shows the behavior of ECM-n heat flow after injection of enzyme-calcite solution under two different temperatures. Both peaks are visible within 6 minutes and then tend to reach a plateau. [Figure 21A] 14 is an infrared thermal image showing the thermal effect of cured ECM-n at different temperatures, showing that the laser heating experiment was set up at ambient temperature for ECM-n. [Figure 21B] 13 is an infrared thermal image showing the thermal effect of cured ECM-n at different temperatures. FIG. 14 shows the spatial view of ECM-n upon 1 hour of laser irradiation. [Figure 21C] 14 is an infrared thermal image showing the thermal effect of cured ECM-n at different temperatures. 15 shows a side view of the sample at 1 hour of laser irradiation. [Figure 21D] 14 is an infrared thermal image showing the thermal effect of cured ECM-n at different temperatures. The laser heating process of ECM-n in a -20°C freezer is shown, and the temperature of the top surface of the sample was increased to 60°C in 10 minutes. [Figure 22] 13 is a graph showing a comparison of experimental and simulated laser heating of ECM-n. Temperature varies along with time and laser power for ECM-n over a 30 minute period. The laser is removed at 20 minutes and the material begins to cool to ambient temperature. Results from the experiment and predictions show reasonable agreement. [Figure 23A]Schematic of the self-repairing ability of ECM-n-beam via laser-induced heating. A trace amount of calcium-enzyme solution was added to the destroyed area, and then ultrapure CO2 was bubbled through the surface for 15 min. 3W laser treatment was carried out on the same spot for 4 h. The high temperature area (white) with a heterogeneous shape gradually becomes circular. [Figure 23B] 13 shows μ-CT scan images of the fractured and laser repaired ECM-n beams in the front, center and back layers. [Figure 24A] Comparison of multiscale microstructure and mineralization of ECM-n (left) and ECM (right). [Figure 24B] Comparison of multiscale microstructure and mineralization of ECM-n (left) and ECM (right). Optical image of laser-hardened ECM-n showing skeletal cross-linking and even distribution of calcite crystals. [Figure 24C] Comparison of multiscale microstructure and mineralization of ECM-n (left) and ECM (right). Optical images of oven-cured ECM showing skeletal cross-linking and even distribution of calcite crystals. [Figure 24D] Comparison of multiscale microstructure and mineralization of ECM-n (left) and ECM (right). SEM image of laser-hardened ECM-n showing skeletal cross-linking and even distribution of calcite crystals. [Figure 24E] Comparison of multiscale microstructure and mineralization of ECM-n (left) and ECM (right). SEM image of oven-cured ECM showing skeletal cross-linking and even distribution of calcite crystals. [Figure 24F] A comparison of the multiscale microstructure and mineralization of ECM-n (left) and ECM (right) is shown. High magnification SEM images of scaffold crosslinks formed by laser curing are shown. [Figure 24G] A comparison of the multiscale microstructure and mineralization of ECM-n (left) and ECM (right) is shown. High magnification SEM images of scaffold crosslinks formed by oven curing are shown. [Fig. 24H] Comparison of multiscale microstructure and mineralization of ECM-n (left) and ECM (right), showing nanoparticle distribution in the matrix. [Figure 24I] Comparison of multi-scale microstructure and mineralization of ECM-n (left) and ECM (right). EDS map images of main chemical composition are shown. [Figure 25A] The compressive strength of laser-repaired ECM-n with different defects is shown. ECM-n samples with different defect geometries are compared to repaired and oven-cured ECM. The laser repair paradigm of ECM-n is presented. The compressive strength of the ECMs, from left to right, are oven-cured ECM (n = 12, blue, M = 9.56, SD = 1.49), laser-cured ECM-n (n = 10, brown, M = 9.45, SD = 1.44), oval defect ECM-n (n = 10, gray, M = 6.69, SD = 1.92, P = 0.003), circular defect ECM-n (n = 10, yellow, M = 6.76, SD = 1.79, P = 0.004), repaired oval defect ECM-n (n = 10, light blue, M = 9.76, SD = 1.86, P = 0.43), and repaired circular defect ECM-n (n = 10, green, M = 9.47, SD = 1.75, P = 0.48). [Figure 25B]Compressive strength of laser-repaired ECM-n samples with different defects was compared to repaired and oven-cured ECM. Average results are shown above each data set and a typical sample is shown at the bottom. The compressive strength of the ECMs, from left to right, are oven-cured ECM (n = 12, blue, M = 9.56, SD = 1.49), laser-cured ECM-n (n = 10, brown, M = 9.45, SD = 1.44), oval defect ECM-n (n = 10, gray, M = 6.69, SD = 1.92, P = 0.003), circular defect ECM-n (n = 10, yellow, M = 6.76, SD = 1.79, P = 0.004), repaired oval defect ECM-n (n = 10, light blue, M = 9.76, SD = 1.86, P = 0.43), and repaired circular defect ECM-n (n = 10, green, M = 9.47, SD = 1.75, P = 0.48). [Figure 26A] Illustrates an Ashby plot of embodied CO2 versus embodied energy data. [Figure 26B] Carbon footprint and mechanical properties of ECM / ECM-n compared to different construction materials. Ashby diagram of specific strength vs. embodied CO2 for comparison with related construction materials. [Figure 26C] Scale-up of the ECM-n procedure is shown. A procedure for producing ECM-n at a construction site is shown. [Figure 27] Photographs of incandescent light curing of ECM-n samples are shown. The ECM-n samples were cured at ambient conditions for 12 hours. [Figure 28A] Comparison of mass loss over curing time between ECMn and ECM. Change in sample mass over time for ECM-n cured with a 3 W laser at room conditions versus ECM. Data for ECM and ECM-n were taken from a median group of 5 independent samples (n=5). [Figure 28B]Figure 1 shows a comparison of temperature over cure time between ECMn and ECM. Temperature as a function of full cure time at the center of a 12.5 mm ECM-n sample surface under 3 W laser induction compared to EICM without nanoparticles. Data presented by median of sample size 3. [Figure 29A] Thermo-mechanical modeling of ECM-n is shown. Predicted 3D temperature contours and comparison of maximum temperatures between experimental data and predictions presented for ECM-n samples with different laser powers. Heat transfer calculations were performed for three different powers. FEM mesh of ECM-n is shown. [Figure 29B] Thermo-mechanical modeling of ECM-n. Predicted 3D temperature contours and comparison of maximum temperatures between experimental data and predictions presented for ECM-n samples with different laser powers. Heat transfer calculations were performed for three different powers. A Gaussian profile of order 1 is shown. [Figure 29C] Thermo-mechanical modeling of ECM-n. Predicted 3D temperature contours and comparison of maximum temperatures between experimental data and predictions presented for ECM-n samples with different laser powers. Heat transfer calculations were performed for three different powers. A 3D view of ECM-n showing temperature contours for 20 minutes with 3W laser irradiation is shown. [Figure 29D] Thermo-mechanical modeling of ECM-n. Predicted 3D temperature contours and comparison of maximum temperatures between experimental data and predictions presented for ECM-n samples with different laser powers. Heat transfer calculations were performed for three different powers. Top view of ECM-n showing temperature contours for 20 minutes with 3W laser irradiation is shown. [Figure 30A] 1 shows a comparison of ECM-n samples that were self-repaired in the presence of carbonic anhydrase, while the disrupted samples were repaired without the enzyme by calcium solution and CO2. [Figure 30B] 1 shows a comparison of ECM-n samples that were self-repaired in the presence of carbonic anhydrase, with the disrupted sample repaired with calcium solution and CO2 along with the enzyme. [Diagram 31]Normalized Raman spectra of four different spots on the cured ECM-n surface. The peak analysis was processed and plotted by Gaussian function fitting. Calcite and γFe2O3 positions are indicated in the figure. [Diagram 32] Powder X-ray diffraction (pXRD) analysis of the enzymatically produced calcium carbonate in the presence of laser induction is presented, including a comparison with a reference spectrum of calcite, which confirms the crystalline nature of the product after laser hardening that results from the enzymatic repair method. [Diagram 33] Photograph of a concrete slab with a 45mm x 4mm x 17mm dent, 3 inches long and 3 inches wide, that was completely repaired. The concrete slab was placed between two platforms so that the dent was floating. Gelatinous carbonic anhydrase was applied to the dent, the dent was allowed to air dry, and the solution was reapplied to the dent. The process of applying the solution and air drying was repeated for 5 days. The dent was observed to be completely repaired in 7 days. [Figure 34A] Photograph of a 7 inch long and 4 inch wide concrete slab with a fully repaired dent measuring 60 mm x 5 mm x 40 mm. Caliper measurements show the dent length to be approximately 56.4 mm. The concrete slab was placed between two platforms so that the dent was floating, as shown in FIG. 34B. Gelatinous carbonic anhydrase was applied to the dent, the dent was allowed to air dry, and the solution was reapplied to the dent. The process of applying the solution and air drying was repeated for 5 days. The dent was observed to be fully repaired in 14 days. [Figure 34B] 34A is a photograph of a concrete slab 7 inches long and 4 inches wide with a fully repaired dent measuring 60 mm x 5 mm x 40 mm. The concrete slab was placed between two platforms so that the dent was floating, as shown in FIG. 34B. Gelatinous carbonic anhydrase was applied to the dent, the dent was allowed to air dry, and the solution was reapplied to the dent. The process of applying the solution and air drying was repeated for 5 days. The dent was observed to be fully repaired in 14 days. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Detailed Description Negative-emitting enzymatic construction materials (ECMs) with self-healing capabilities can be used as replacements for concrete and Portland cement. In the disclosed approach, carbonic anhydrase (CA) is employed to catalyze the covalent condensation of carbon dioxide and water or fixation of carbon dioxide from the atmosphere to promote the precipitation of calcium ions as calcium carbonate crystals in aqueous solutions. The result is a functional and biological ECM with compressive strength and Young's modulus properties more than twice those of cement mortar and other alternative building materials. The growth of mineral bridges that hold sand particles together is modeled and studied. This approach provides a valuable route for environmentally friendly construction materials.

[0020] The compositions herein refer to carbon negative self-repairing construction materials compounds that include an amount of aggregates such as sand and gravel, a catalyst such as an enzyme, a scaffolding material with a crosslinking agent, and a calcium source.

[0021] The mixture containing the enzyme is configured to cross-link sand particles in a quantity of aggregate forming a dense solid mass. This enzyme-induced method of cross-linking sand particles results in a dense, hard, strong, and tough structural material that is also capable of repeatedly self-repairing when exposed to a calcium source and CO2. As used herein, the terms catalyst and enzyme are used interchangeably.

[0022] The production of ECM adsorbs CO2 and therefore can be used for carbon sequestration as well as reducing 9% of the current global CO2 emissions caused by concrete production and repair. The material is environmentally friendly, odorless, harmless to humans and other organisms, and has the highest mechanical strength (about 12 MPa) reported for an alternative construction material. The curing process of ECM (a few days at ambient temperature) is also significantly faster compared to 28 days for conventional concrete.

[0023] One aspect of the invention described herein provides a self-repairing building material compound, the compound comprising an aggregate material, a catalyst such as an enzyme, a scaffolding material, and a calcium source. In one embodiment of the compound, the compound is a carbon negative compound.

[0024] In one embodiment of the compound, the aggregate material further comprises sand aggregate. In one embodiment of the compound, the scaffolding material further comprises a cross-linking agent selected from glutaraldehyde and tannin. In one embodiment of the compound, the scaffolding material comprises a polymer. In one embodiment of the compound, the scaffolding material is gelatin. In one embodiment of the compound, the catalyst is an enzyme such as carbonic anhydrase or a chemical analogue of carbonic anhydrase or synthetically produced carbonic anhydrase.

[0025] An embodiment of the compound further comprises a source of carbon dioxide. In an embodiment of the compound, the compound sequester atmospheric carbon dioxide. The compound has a mechanical strength of at least 10 MPa to at least 16 MPa.

[0026] An embodiment of the compound further comprises at least one of a light source, a heat source, a laser source, and a source of applying a magnetic field. In an embodiment of the compound, the compound is configured to form mineral bridges between aggregate materials to obtain a dense mass. In an embodiment of the compound, the catalyst is configured to operate at a pH of 6.5 to 8.5 and at a temperature of 30° C. to 50° C. An embodiment of the compound further comprises a quantity of nanoparticles.

[0027] One aspect of the invention described herein provides a method of forming a carbon sequestering construction material, the method includes preparing a solution having a catalyst and a calcium solution, mixing an aggregate material with a framework forming material to obtain a slurry, and adding the catalyst solution and the calcium solution to the slurry, whereby the CA or analog utilizes atmospheric carbon dioxide, i.e., ambient carbon dioxide, and calcium from the calcium solution to form calcium carbonate crystals, thereby sequestering carbon and obtaining a carbon sequestering construction material.

[0028] In one embodiment of the method, calcium carbonate crystals are deposited on the aggregate material to form mineral bridges. One embodiment of the method further comprises dehydrating the building material to promote bridges, including between the scaffolding materials. In one embodiment of the method, the calcium solution is configured to promote the continuous precipitation of calcium carbonate crystals.

[0029] One aspect of the invention described herein provides a carbon negative self-repairing construction material compound, the compound comprising an amount of aggregate sand, an amount of carbonic anhydrase catalyst, a gelatin scaffolding material, a calcium solution, and an amount of iron oxide nanoparticles. One embodiment of the compound further comprises a laser or light source for curing the compound.

[0030] The majority of infrastructure is made of concrete. One ton of CO2 is released into the atmosphere for every ton of concrete produced. As a result, the concrete industry is the second largest industrial source of CO2, accounting for about 9% of global emissions. The invention described herein presents a novel Enzymatic Construction Material (ECM) with superior mechanical properties to concrete mortar. Its manufacturing method requires about 48 hours, which is significantly faster than current methods of manufacturing building materials, including assemblies based on biological methods, has a longer curing period, and mechanical properties less than half that of ECM.

[0031] Thus, ECM is an alternative to cement that crosslinks sand particles with a lightweight and inexpensive polymer backbone through the precipitation of calcium carbonate crystals, resulting in a hard, solid material that is twice as strong as cementitious substrates and self-heals from repeated large-scale crack developments through the incorporation of enzyme catalysts. In contrast, cementitious materials or other current building materials do not have similar capabilities. The most advanced active building material is Living Building Material (LBM), which uses photosynthetic cyanobacteria or fungi to precipitate calcium carbonate crystals. The production of LBM is inefficient because the cost of the bacteria is significantly higher than ECM and the process is not easily operationalized for large-scale production. Most importantly, the self-healing ability of LBM is limited and the material cannot recover its original strength. LBM can also produce antibiotics such as polymyxins and refractory bacteria that may be biohazardous.

[0032] The invention described herein is developed by applying a biological method of repairing concrete through the precipitation of calcium carbonate. Natural enzymes are safe and reliable proteins that rapidly catalyze chemical reactions without being consumed in the process. Carbonic anhydrase (CA) is a fundamental enzyme found across all species. Fourteen isoenzymes of CA have been found in the human body. The structures, properties and tissue distribution of different CA isoenzymes are different; however, the isoenzymes have the same important physiological function in cellular respiration by reacting CO2 with water in body tissues to produce carbonic acid and reversing the reaction in the lungs to produce CO2.

[0033] CO2 sequestration is based on chemical fixation in carbonate minerals such as calcite, aragonite and magnesite. The invention described herein utilizes a biomimetic CO2 uptake mechanism using biocatalysts such as CA to reduce local CO2 concentrations emitted by cement production.

[0034] Despite many attempts to create functional concrete, such as using enzyme-catalyzed calcium carbonate precipitation to repair concrete, preparing self-healing concrete containing bacteria, or high-cost self-healing concrete containing capsule systems, they have not been able to break away from the paradigm of consuming concrete cement materials as a matrix. To fundamentally solve the CO2 generation problem associated with concrete production, sustainable alternative materials to cement are needed.

[0035] Microbially Induced Calcium Carbonate Precipitation (MICP) technology demonstrates the continuous regenerative potential of applying the photosynthetic cyanobacterium Synechococcus in MICP and involves the development of a long-term sustainable building material (LBM) that is an alternative to concrete cement materials. However, the mechanical properties of LBM are not comparable to natural concrete cements, making this material far from practical construction applications. The mechanism of crystal precipitation and growth in the bioscaffold is also inefficient, which results in a low density material. The bacteria may require maintenance to continue viability.

[0036] The examples described herein present a faster and more efficient method to form negative emission self-repairing construction materials using sand aggregates, trace amounts of enzymes, small amounts of scaffolding materials including crosslinking agents, and a calcium source. The material can be cured at high temperatures for short periods or at room temperature for long periods. This enzyme-induced method of crosslinking sand particles results in a dense, hard, strong, and relatively tough structural material that can also repeatedly self-repair with exposure to a calcium source and CO2. The enzyme used to generate the novel material, carbonic anhydrase (CA), can be easily stored and stable at pH 6.5-8.5 and temperatures between 30-50°C. The reaction conditions promote enzyme stability, consume CO2, and generate an environment where harmful reagents and pollutants are avoided. The mechanism of crystal growth in the scaffold results in excellent mechanical properties and self-repairing capabilities due to the catalytic effect of CA. This enzyme-catalyzed process, the structural fabrication process, and the 2D microstructure of the material, called Enzymatic Construction Material (ECM), are shown in Figure 1 as a schematic.

[0037] Concrete production and waste has a significant impact on global pollution. Enzymatic Construction Materials (ECMs) are low-cost, environmentally friendly construction materials that provide better mechanical properties than concrete through enzyme-catalyzed crystal precipitation. The examples described herein show carbonic anhydrase (CA), an enzyme derived from biological cells, which promotes the carbonation reaction by converting carbon dioxide to precipitate calcium carbonate crystals. In some embodiments, synthetic analogs of CA are used as catalysts or enzymes. The polymer backbone (gelatin) provides a skeletal framework for the crystals to form and establish strong crystalline bridges that bind the sand particles. The presence of enzyme molecules as catalysts allows the ECM to have self-repairing capabilities. The examples described herein show that the ECM can withstand six repair cycles of being damaged at specific points, resulting in a loss of about 50% of the overall strength. Thus, ECMs are a sustainable alternative to concrete, the most used material worldwide. ECMs have unlimited potential for the formation of environmentally friendly construction materials and space construction materials.

[0038] The examples described herein introduce a novel paradigm to develop a self-repairing negative emission type construction material named Enzyme Construction Material or ECM using sand, calcium, gelatin and trace amount of carbonic anhydrase. ECM has exceptional mechanical properties as a construction material with higher compressive strength (12 MPa) than any other available method and twice as high as cement mortar. Therefore, ECM can be used to repair or even replace Portland cement concrete. The examples described herein investigated the effect of CA enzyme catalyst, high pH condition and gelatin on the overall reinforcing and toughening mechanism of ECM. The data show that wider and longer mineral bridges are incorporated into the microstructure of ECM compared to samples without enzyme and / or base samples. The bridges reinforce and toughen the material.

[0039] The self-repairing ability of ECM was investigated by cyclical destruction routine and repair examples, and ECM samples survived six destruction cycles. Therefore, the enzyme mineralization method is useful for the formation of negative emission construction materials and carbon sequestration methods. ECM can be rapidly manufactured in an environmentally friendly manner and is therefore an alternative to current building materials.

[0040] The ECM requires only a small amount of low-cost polymer as a backbone, and incorporates only trace amounts of enzymes to produce a material that is odorless, inexpensive, environmentally friendly, and mechanically strong. The ECM can self-repair even after multiple damage cycles at the same location, demonstrating strong self-repairing ability. In some embodiments, the ECM is cured by baking at low temperatures. In an alternative embodiment, the ECM is cured by light. In other embodiments, the ECM is cured by application of a magnetic field.

[0041] ECM is a negative emission structural material with self-healing ability that further enhances its durability and, consequently, its negative carbon footprint. The material can essentially be used as an alternative carbon sequestration method. ECM alleviates the high monetary and energy costs associated with the production and use of concrete, while consuming carbon dioxide, a greenhouse gas. Most importantly, ECM does not use any hazardous reagents with bad odors that would limit the application of the final structure. Thus, ECM provides a novel, low-cost, safe and highly efficient method for forming sand slurry materials with strong self-healing ability. ECM is a novel material and method for the development of environmentally friendly construction materials. Thus, the enzyme self-healing construction material is a negative emission material that consumes CO2 during its production and during its self-healing process.

[0042] Conventional concrete curing requires 28 days with adequate amount of water for continuous hydration to achieve mechanical strength. Compared to concrete, ECM achieves maximum compressive strength in 24 hours in oven heating or more than one week under natural drying. However, using ovens to reduce time cost makes on-site construction difficult. The embodiments of the invention described herein show that adding trace amounts of iron oxide nanoparticles to ECM produces an improved material called ECM-n, which is cured with low power laser or incandescent light (FIG. 27). Based on the research of laser-induced nanoparticle application in hyperthermia, this method utilizes the exothermic behavior of iron oxide nanoparticles under external electromagnetic (radio frequency, microwave and laser) excitation. Notably, ECM-n samples cured in 12 hours under irradiation of 3W laser (808 nm wavelength) have similar compressive strength as ECM. Acceleration of repair by laser irradiation was also observed when large defects were formed in ECM-n samples, and the samples regained mechanical strength and properties comparable to the original defect-free samples.

[0043] Some of the embodiments described herein have been published in Matter Volume 5, Issue 3, March 2, 2022, Pages 957-974 by co-inventors Shuai Wang, Suzanne F. Scarlata, and Nima Rahbar as "A self-healing enzymatic construction material", which is incorporated herein by reference in its entirety. Other parts of the embodiments described herein have been submitted as manuscripts by co-inventors Shuai Wang, Suzanne F. Scarlata, and Nima Rahbar to Cell Reports Physical Science as "Curing and self-healing of enzymatic construction materials using nanoparticles", which is incorporated herein by reference in its entirety.

[0044] The present invention described herein is the most practical method. However, it is recognized that deviations may be made within the scope of the present invention and that modifications may occur to those skilled in the art. With respect to the above description, it should be recognized that the optimal dimensional relationships of the components of the present invention, including variations in size, material, shape, form, function, steps, and operation, assembly, and mode of use, will be apparent to those skilled in the art, and all equivalent relationships to those shown in the drawings and described herein are intended to be encompassed by the present invention.

[0045] The following examples and claims are merely illustrative and are not intended to be further limiting. Those skilled in the art will recognize or be able to ascertain, without more than routine experimentation, many equivalents to the specific procedures described herein. Such equivalents are within the scope of the present invention and the claims. The contents of all references cited in this application, including issued patents and published patent applications, are hereby incorporated by reference.

[0046] The invention now described in detail is further illustrated by the following examples and claims. EXAMPLES

[0047] Example 1: Enzyme solution preparation Analytical grade carbonic anhydrase (CA), calcium chloride dihydrate, and tris(hydroxymethyl)aminomethane (THAM) were obtained from Sigma Aldrich chemical company. To prepare the enzyme matrix solution, 2.9 mg of CA and 1 mL of deionized water were mixed in an aliquot and then shaken horizontally for 2 min uniformly. The CA solution (5 L of 100 M CA) was pipetted into each of the empty aliquots and stored in a freezer.

[0048] Example 2: Calcium Carbonate Solution Preparation To prepare the buffer solution, 0.1M Tris (ordered from Sigma Aldrich) was added to 200mL of deionized water and mixed with the 2M saturated solution and stirred for 2 minutes. Calcium chloride dihydrate was chosen as the calcium source because it can generate calcium carbonate more efficiently. The high concentration of free calcium ions in the solution facilitates the dissolution of calcium chloride dihydrate. Once the calcium chloride dihydrate has substantially dissolved, 10L of 100M CA solution was added to a 1000mL beaker and stirred for another 2 minutes. CO2 gas was then introduced into the solution at a rate of 5 bubbles per second for 10 minutes. The entire process was recorded using a pH meter. After 5 minutes, some fog was observed emerging from the solution. The experiment was terminated when the pH reached 7 and the flow of CO2 gas was stopped. The solution was then left to stand for 4 hours and the supernatant was siphoned off to prepare a highly concentrated calcium carbonate solution.

[0049] Example 3: Preparation of cubic and rectangular ECM samples Cuboid samples (25 mm) were prepared for uniaxial compression testing. A loading rate of 1.27 mm / s was selected. One-sided concave beam samples were prepared for fracture testing and flat beams for bending testing. 10% gelatin by weight (gelatin / solution) was mixed with sand for 2 min. Gelatin was selected for its chemical affinity with CA and because its complete solubility temperature is 35°C, which is within the temperature range of carbonic anhydrase activity. The sand-gelatin mixture was then placed in a silicone mold. Calcium carbonate solution was then titrated onto the sample surface. The samples were allowed to rest for 30 min until the solution was completely saturated in the matrix. The ECM samples were then dried in an oven at 100°C for 24 h and demolded for testing.

[0050] Example 4: Weight Gain Four groups of solutions were prepared in a similar manner as described in the enzyme solution preparation (Ca:Ca 2+ , BCa: base + Ca 2+ , BEC: base + CA + Ca 2+ , ECa: CA+Ca 2+ The solution was then aerated with CO2 gas (5 bubbles / sec) for 10 min with continuous stirring. The weight of the solution was measured immediately after the experiment.

[0051] Example 5: Self-repair experimental procedure To investigate the self-repairing ability of ECM, one-sided recessed beam samples were prepared in a similar manner as presented in the cube and rectangular sample fabrication process section. The first cycle was started with the beam sample that was broken in a three-point bending test and then placed back into the silicon mold. To demonstrate the self-repairing process, a certain amount of 2 mL of calcium-enzyme solution was evenly titrated on the surface of the cracked area. CO2 gas was then bubbled through the rubber tube at a constant pressure on the cracked surface for 10 min. The sample was then dried in an oven at 100 °C for 24 h and then subjected to a three-point bending fracture test. The fracture / repair procedure was repeated six times and data was collected.

[0052] Example 6: Glutaraldehyde Modification Glutaraldehyde at a concentration of 50% was obtained from TCI AMERICA as an ECM crosslinking agent. A 1:1 weight ratio of gelatin and glutaraldehyde was then added onto the surface of the ECM samples. The samples were left at room temperature for 30 minutes until the gelatin / glutaraldehyde solution completely penetrated the samples. The samples were then allowed to dry for an additional 24 hours and then mechanically tested.

[0053] Example 7: X-ray diffraction (XRD) and FT-IR analysis Analysis of the dried enzyme solution product was performed by powder X-ray diffraction (pXRD) and Fourier transform infrared spectroscopy (FT-IR) to confirm both chemical composition and crystallinity. pXRD was performed at 25 °C on a Bruker AXS D8 Focus (Bruker, Billerica, MA, 102 of 190 USA), pXRD spectra were performed using a CuKa radiation source at 40 keV and 40 mA from 2θ of 20° to 90° with a step size of 0.100° relative to the baseline, and FT-IR was performed on a Bruker Optics Vertex 70 equipped with a Specac Golden Gate Diamond Single Reflection ATR element (Bruker, Billerica, MA, USA). Calcium carbonate prepared from the enzyme solution was rinsed and dried for analysis. Figure 12 compares the pXRD spectrum against a reference spectrum of calcite, and Figure 13 compares the FT-IR spectrum of the dried enzyme product against a baseline FT-IR spectrum of Ca-carbonate from the RUFF Project database. Both results confirm the chemical composition and crystallinity of the enzyme product as that of calcite.

[0054] Example 8: Compressive strength of cubic coarse sand ECM Unconfined compression experiments were performed on ECM samples with coarse sand (NO. 30, sand remaining on the 600 μm sieve was used as a substitute sand to be mixed into the material) according to the American Society for Testing and Materials (ASTM) standard, because the ECM design showed the highest compressive strength compared to the intact and high pH samples in the extensive fine sand experimental design. The average strength of the coarse sand ECM was 4.2 MPa, which is lower than the fine sand ECM (Figure 4D). The main reason is that the compressive strength in these samples is influenced by the sand aggregate strength, size and distribution, which is larger than the crystal bridge size.

[0055] Example 9: Break and bending tests The results of the three-point fracture experiment are shown in Figures 15A-15C. The fracture experiment was performed using the method in the ASTM standard. A cured silicone mold with a sharp crack was prepared and used for sample preparation. A four-component solution of 10 ml of CA enzyme, Tris base, 2M calcium chloride dihydrate, and DI water was prepared. This was then mixed thoroughly for 2 minutes and CO2 gas was bubbled through for 10 minutes. The solution was then titrated onto the coarse sand sample and allowed to sit for 30 minutes until it completely penetrated the sand. The sample was then placed in a 100°C oven for 24 hours and then demolded. The fracture toughness was then calculated after the fracture experiment. The higher fracture energy indicated that the material exhibited more ductile fracture. The data shows that the coarse sand ECM sample had the highest average fracture energy (218N / m).

[0056] Example 10: Crystalline bridge growth mode In a supersaturated calcium chloride solution, the gelatin backbone provides a stable platform for crystal nucleation and growth. The dissolved calcium carbonate then continues to precipitate around the crosslinks, which results in a lower ambient concentration of calcium carbonate than in the system as a whole. The dissolved CaCO3 that precipitates at the gelatin surface is R The molar concentration of crystals in a solid mineral is expressed as C rThe molar concentration of CaCO3 in solution immediately surrounding the solid mineral is C0, which is very low. Dissolution of calcium carbonate is difficult due to its solubility of only 13 milligrams per liter. The concentration profile is shown in Figure 17A. The three defined concentrations are C r >C R ≫C0, where the number of CaCO3 molecules (dN) that migrate towards the interface to form mineral bridges is given by Fick's first law within a time interval dt:

number

[0057] As the mineral bridge interface advances a distance dr in a time interval dt, the change in the number of dissolved CaCO3 molecules in the mineral bridge is expressed as: dN=(C r -C0)(2πrdz)dr (2)

[0058] Equating equations 2 and 3 gives the following:

number

[0059] ∂C / ∂r is further estimated by the simplified linear concentration profile shown in FIG. 17B as follows:

number

[0060] Therefore, equating the number of moles of CaCO in these two shaded areas A and B gives:

number

[0061] L is obtained as follows:

number

[0062] Using the above formula, the growth rate of mineral bridges is given by

number

number

[0063] If the thickness of the mineral bridge is defined as H=rR, then Equation 9 can be rewritten as:

number

[0064] The initial condition is H(t=0)=0, where C r / C R =α, H / R=Y and Dt / R 2 If you set =X, the result is as follows.

number

[0065] Finally, we set the boundary conditions such that when t=0, X=0, and integrate Equation 10 from 0 to X, resulting in

number

[0066] Therefore, crystals start to precipitate within a few seconds, so the initial time t0 cannot be equal to 0. Assumed experimental parameters: R = 200 μm, α = 4.8, and D = 1.6 × 10 -9 m 2 / s. The thickness of the mineral bridges as a function of time is plotted in Figure 8. The experimental results are consistent with the presented model.

[0067] Example 11: Enhanced ECM-Tannin Modification Tannin was added to the ECM at 0.8% by weight of the sample. This value is much higher than the usual ratio in the modification of gelatin systems to achieve stronger cross-linking. The gelatin-tannin system can form stronger bonds faster than the gelatin system. However, the performance of cross-linking in compression is not as good as that in tension. Powdered wine tannin from Midwest Homebrewing and Winemaking Supplies. Inc. was selected. Tannin, 28% of the gelatin weight, was mixed with gelatin and sand particles by hand and stirred for 2 minutes. Calcium carbonate solution was prepared as described for the previous experiment and heated to 35°C. The matrix was then poured into a cube silicon mold and 7 mL of the solution was pipetted into each cube. The samples were then dried before performing the compression test.

[0068] Example 12: Catalytic performance CA is the fastest known enzyme with a high catalytic rate of CO2 in a diffusion-controlled process. The method of forming ECM is based on CA catalyzing the rapid precipitation of CaCO3 to form mineral bridges that bind sand aggregates in two separate steps: First, CA catalyzes the reversible hydration of carbon dioxide to bicarbonate (Equation 13), then reacts with calcium ions in solution to precipitate CaCO3 (Equation 14). Synthetic CA analogs mimic the CA reaction. However, synthetic analogs may be less efficient and must be used at higher concentrations to achieve similar results.

[0069] The efficiency of the reaction depends on four basic factors: (1) the concentration of calcium available at the nucleation sites. Catalysis by CA enzymes shows high biomineralization efficiency where calcite crystals (CaCO3) self-assemble into the sand-gelatin matrix to form "bridges" between the sand particles, where gelatin serves as a harmless and odorless scaffold that provides strength through physical cross-linking after dehydration. It can be considered as a carrier of the crystals that binds the entire microstructural system. [ka]

[0070] There is enough ambient carbon dioxide in the air to drive the main chemical reactions mentioned above. The reaction between carbon dioxide and water is reversible, but both sides of the reaction proceed simultaneously to achieve a "dynamic equilibrium" that prevents the precipitation of calcium carbonate crystals. In this process, carbon dioxide dissolves in water to form carbonic acid, while chloride ions from calcium chloride produce hydrochloric acid, which forms calcium carbonate and hydrochloric acid as the reaction proceeds. Buffers are often added to prevent a drop in pH and to promote the precipitation of calcium carbonate crystals. According to Le Chatelier's principle, the equilibrium will shift in the direction of reducing hydrogen ions. In other words, the direction will shift toward the direction of producing weak acid molecules. Conversely, when a weak acid is added to a strong acid salt solution, the change in the concentration of hydrogen ions in the solution will not produce the strong acid, since the strong acid does not have an ionization equilibrium. Therefore, when balancing the solution, a Tris buffer is added to the reaction to ensure constant precipitation of calcium carbonate crystals. The buffer solution is composed of a weak acid, "HA," and its own salt, "NaA."

[0071] A buffer solution is a solution containing sufficient alkali, "A", to buffer strong acids in solution. - " ions. When a certain amount of strong acid is added to a solution, H + AEON is "A -" ions, and the pH value of the solution remains constant. Therefore, calcium carbonate crystals can be precipitated well. As a first step in the development of the material, the efficiency of CA was quantified by measuring the weight gain due to the precipitated crystals produced by the enzyme reaction. The results of the weight gain from four different solutions are shown in Figure 2. "Ca" represents the aqueous solution containing only calcium source, "BCa" represents the base and calcium source solution, "BEC" represents the base, CA enzyme and calcium source solution, and "ECa" represents the gelatin-free sand slurry system with only CA enzyme and calcium source added to the solution.

[0072] These data show that within the same time range, the ECa sample obtained the highest average weight gain of about 0.82 g, which is higher than the BEC sample at about 0.07 g and significantly higher than the Ca sample at about 0.24 g. The results indicate that the enzyme-catalyzed carbonation is efficient and the calcium crystallization ability in ECa is the highest in this group. It should be noted that the weight gain is not equal to the amount of precipitated crystals, but indirectly reflects the catalytic ability of the enzyme to convert carbon dioxide. The weight gain in each solution is equal to the amount of absorbed CO2, which is used to calculate the weight of precipitated calcium carbonate based on Equations 13 and 14. Catalytic efficiency K of CA at 25°C and pH=9 cat is approximately 10 rec / s, which is defined as the CO hydration exchange times and is the maximum number of substrate molecules that can be converted to products by a single CA per second.

[0073] [Table 1]

[0074] The theoretical and experimental results are compared in Table 1. The theoretical result for a CO2 molecule is 3.49 × 10 23 and the molecular weight of the experiment for the CO2 molecule is 1.12 × 10 22 and the effect of experimental error and carbon dioxide on pH (K catTaking into account the pH-dependent changes in carbonation, the experimental results were in good agreement with the predicted results at ambient temperature conditions, and the enzyme did indeed improve carbonation.

[0075] Comparing the BCa and Ca samples in Figure 2, it was observed that an additional amount of crystals precipitated after adding the base reagent to the solution. From Equation 13, the hydroxide ions neutralize the hydrogen ions in the solution, driving the reaction forward. Urease uses the nitrogen source urea to generate hydroxide ions to increase the pH of the solution, which causes calcium carbonate to precipitate from the calcium ions in the solution.

[0076] CA-mediated calcium carbonate precipitation was compared with the urease method, including mechanical properties and structure formation. The sand-free calcium carbonate formed by the urease slurry is a non-uniform crystalline structure, however, the calcium carbonate from the CA slurry is organized and uniform in layers. The calcium carbonate in the CA method adheres to the sand particles to form an organized and uniform layered structure, likely due to the finding that faster production of the precipitate reduces the mobility of the solid particles. In terms of mechanical properties, the CA sample also outperforms the urease sample in both compressive strength and tangent modulus parameters. These experiments show that the CA material and method of use are more effective in mineral precipitation and assembly of sand slurry construction materials than the other materials tested.

[0077] Example 13: Microstructural characterization To understand whether the composition and morphology of the ECM was affected by the presence of CA enzyme, four different compositions were used to evaluate mineral deposition, mineral distribution, structural arrangement and cross-link size, which differed in high pH, ​​no CA enzyme and no calcium source. The control "GL" (gelatin) sample contained ECM (CA + gelatin + Ca 2+ ) but contained only gelatin. 2+) represents the high pH control group, where the higher pH aids in the production of a larger proportion of calcium carbonate. 2+ ) samples show the effect of CA enzyme on crystal precipitation and the microstructure of the resulting product made with gelatin and a calcium source.

[0078] Compared to the other three groups, the structure of the ECM was observed to be denser and more organized. The surfaces of the GL and GCa samples were found to be smooth, and their bridges in some domains were too short or too fine. The mineral bridges in the BGE are stronger, but the overall arrangement of the structure is irregular. During the preparation of the ECM, most of the calcium carbonate crystals are trapped or encased in the gelatin, forming bridges, and it is difficult to directly observe the crystal distribution on the surface with SEM. The samples were then analyzed by energy dispersive X-ray spectroscopy (EDS). EDS allows to qualitatively determine and locate the crystals by their calcium content. The results of the Ca2+ distribution from the EDS analysis are shown in Figure 3. No calcium was added, so no calcium was observed in the EDX map of the GL sample. EDS revealed a dense distribution of calcium in the ECM, which contributed to thicker and wider bridges covering most of the surface of the surrounding sand grains. In samples GCa and BGE, only a small amount of calcium was distributed on the sand surface or in the bridges. 4A and 4B show a close-up view of the cross-linking mechanism between ECa (CA+Ca2+) and ECM samples. Although calcium carbonate crystals form a suitable cross-linking network to cross-link sand particles, the size of the ECa bridges (~80 m) is smaller than that of ECM (150 m), which means that gelatin scaffolding enhances and extends the cross-linking. The crystals align closely in the gelatin, resulting in an organized dense structure that establishes a mechanism for the enhancement of the mechanical properties of the ECM and provides the physical basis for the high durability and corrosion resistance of the resulting product.

[0079] The failure mechanism of ECM depends on the cross-linking in the sand-aggregate component. Figures 4C and 4D show ECM samples after mechanical testing, showing a crack propagating in the cross-direction to the center of the cross-link. Figure 4D shows a typical fractured surface in the crack tip region, exposing a fracture surface of 150 mm in diameter. Figure 4E shows that the sand aggregate is delaminating from the matrix, which is the other main failure mechanism after cross-link failure and was found in the sand-gelatin system. However, this mechanism occurs more frequently in the case of self-repair cycles.

[0080] Example 14: X-ray diffraction (XRD) and FT-IR analysis To investigate the crystallinity and chemical composition of the ECM enzyme products, powder X-ray diffraction (pXRD) and FT-IR were performed at 25 °C on a Bruker AXS D8 Focus (Bruker, Billerica, MA, 102 of 190 USA), and pXRD spectra were obtained using a Bruker Optics Vertex 70 (Bruker, Billerica, MA, USA) equipped with a CuKa radiation source of 40 keV and 40 mA at 20-90 2 with a step size of 0.100 relative to the baseline, and a Specac Golden Gate Diamond Single Reflection ATR element. The results (Figures 12 and 13) demonstrate that the crystallinity of the enzyme products is predominantly composed of calcite.

[0081] The mechanical experiments focused on the compressive strength, tensile and fracture properties of the ECM using groups. Compressive and three-point bending tests were conducted to study the mechanical performance of the proposed enzyme construction material. Five different groups of sand slurry samples were prepared and named as follows: ECa(CA+Ca 2+ ), GCa (gelatin + Ca 2+ ), BGC (base + gelatin + Ca 2+ ), BGE (base + gelatin + CA + Ca 2+ ) and ECM (CA + gelatin + Ca 2+). Note that the above samples contain a calcium source. Compressive strength and elastic modulus are shown in Figures 5A-5E.

[0082] The main function of construction materials such as concrete is compressive strength. The compressive strength of concrete mixture depends on the properties of aggregate and cement mortar matrix. As a potential construction material, ECM also has its own "aggregate" and "mortar matrix", and its mechanical properties are determined by the strength of sand and mineral bridges as well. The results in Figure 5A show that gelatin as a skeleton in GCa can enhance the compressive strength of sand slurry material ECa. However, the average strength of 4.5 MPa is not remarkable in comparison of GCa and ECM. The data show that ECM exerts the highest compressive strength and elastic modulus.

[0083] The average compressive strength of the ECM sample is 9 MPa, which is 2 times higher than that of the GCa sample, 4.7 times higher than that of the ECa sample, and significantly higher than the base-modified samples of BGC and BGE (Figure 5D). The elastic modulus of the ECM is higher than the other samples, which means that the elastic deformation under the same external force is smaller. From the EDS-SEM images in Figure 3, it can be observed that the size of the crystalline bridges in the ECM is about 150 m wide and 50 m long on average. The calcium carbonate crystals in the ECM are also more uniformly distributed. Comparing the EDX maps of the ECM samples with the BGE and BGC samples, a significant amount of calcium was observed in the ECM bridges. Therefore, compared with the structure and mechanical properties of the other three groups, it can be inferred that the crystalline bridges are the main reinforcing and toughening mechanism in these heterogeneous materials.

[0084] It is noted that the compressive strength of the ECM is more than twice that of standard cement mortar (which has a specific strength of 3.5 MPa). Sand slurry cube samples containing coarse aggregate were also produced (Figure 5C) and their compressive strength is shown in Figure 14. The coarse sand slurry ECM shows an average strength that is about 31% higher than the high pH BGE sample and about 17% higher than the control gelatin sample GCa. The CA enzyme plays the same role in both fine and coarse sand samples by increasing the rate of crystal precipitation within a fixed time, which results in strengthening the samples. However, the maximum size of the crystal bridges is limited by the amount of calcium, which prevents the increase in reinforcement of the coarse aggregate beyond a certain threshold. The maximum size of the bridges limits the challenge of bonding larger sand particles, which results in the coarse aggregate samples being relatively weaker than the fine aggregate samples. The size of the crystal bridges in the fine aggregate samples is comparable to the size of the particles, which results in a more even distribution of forces in the microstructure of the material, thus resulting in a higher overall strength and fracture energy, which contributes to a more durable product.

[0085] Example 15: Tensile Test Fracture energy is an important mechanical property of building materials, since crack propagation and control are highly related to the serviceability and durability of materials. Single-sided indentation bending (SENB) tests were conducted on the ECM beam sample shown in Figure 6A, and the fracture test results are shown in Figures 6B and 6C. The fracture energy and load-displacement curves reflect the excellent mechanical properties of ECM. The EDS maps in Figure 3 show that the crosslinks are mainly calcium carbonate crystals incorporated in the gelatin skeleton to crosslink sand particles. The fracture surfaces in Figures 4A-4E also show the typical fracture mechanism in ECM due to particle delamination and crosslink fracture. Thus, the toughening mechanism is mainly by mineral crosslinks. Therefore, ECM with wider and longer crosslinks can exhibit excellent tensile properties. The fracture energy results showed that the application of CA enzyme method significantly increased the fracture energy by about 100% compared to GL and about 77% compared to GCa. The average ultimate load of ECM samples is also about 27% higher than GL samples and about 16% higher than GCa samples. Fracture and bending tests of the coarse sand slurry ECM are shown in Figures 15A-C. The fracture energy of the coarse sand slurry ECM is approximately 38% higher than the control "GCa" and approximately 120% higher than the high pH sample (BGC). There are no other methods of forming a structural sand slurry material with similar compressive strength and fracture energy.

[0086] In sand slurry materials, calcium carbonate crystal bridges are a key factor in providing compressive strength and play a coordinating role in the toughening mechanism. However, the polymer backbone provides the main toughening system. These factors provide the improved durability of the ECM compared to previous materials. Comparing the ECM beam fracture samples with the two control "GL" and "GCa" groups, it was observed that the fracture energy and ultimate tensile load were enhanced by CA enzyme catalysis, and that aggregate type and size may also affect the strength and fracture energy of these materials. However, a similar trend was observed in the examples with coarser aggregate ECM. In the coarse sand ECM samples, the mineralized gelatin matrix plays a significant toughening role. The control group without CA treatment (GCa) shows a lower fracture energy. Under high pH conditions, CA enzyme catalysis has a lesser effect on fracture energy, especially in the coarse sand slurry samples (Figures 15A-C). Although more crystals were precipitated, the effect of the amount of crystals on the toughness of the coarse sand ECM may be less than other factors. In Figures 15A-C, it is observed that the precipitation of more crystals does not increase the toughness of the material in the case of high pH. SEM images show that the calcium-gelatin matrix bridges of ECM are wider and longer than those of non-CA enzyme sample GCa, which plays an essential role in the toughening mechanism in these materials, where fracture is initiated at the bridges in high stress regions. However, since at the macroscale mortar is heterogeneous, there may be other mechanisms that reinforce and toughen the samples. The interfacial fracture toughness between the crystal bridges and the sand surface, which is determined by the surface roughness of the sand grains, may also affect the overall strength and toughness of these materials.

[0087] Although previous publications have noted that high pH conditions may be beneficial to the degree of carbonation, the overall performance of samples with high pH preparations in the tests herein is not as good as that of ECM samples. Within a limited reaction time, the addition of a base reagent produces some calcium hydroxide along with calcium carbonate in the precipitation. Calcium hydroxide consists of one calcium cation and two hydroxide anions on a molecular scale, while calcium carbonate consists of one calcium cation and one carbonate anion, and both calcium hydroxide and calcium carbonate are non-polar. Most of the calcium carbonate (calcite) molecules have a cubic structure at room temperature, which creates a more stable and rigid structure in all directions. However, calcium hydroxide crystals have a planar structure at room temperature and are more fragile. The elastic modulus and strength of calcium carbonate are about 70 GPa, which is higher than that of calcium hydroxide, which are about 48 GPa, respectively. Thus, calcium hydroxide crystals during crosslinking provide inferior advantages compared to calcium carbonate in both compression and tension.

[0088] Example 16: Crystal Growth Modeling Underestimating crystal nucleation and growth is paramount in determining and predicting the physical properties of ECM. Therefore, optical and electron microscopy methods were utilized in detail to study the time course of crystal growth in ECM samples. In Figure 7, the formation of calcium carbonate crystals on the sand-gelatin system surface is analyzed using SEM and optical images. In ECM, the gelatin skeleton and the rough surface of the sand provide many sites for the nucleation reaction of calcium carbonate in the solution. Due to the presence of CO2 as a foreign body in the solution, the crystal growth method is defined by heterogeneous nucleation, so the energy barrier problem associated with preliminary nucleation is inevitable. Here, carbonic anhydrase reduces the activation energy for the reaction barrier. It can be observed from the images that calcium carbonate crystals are immediately formed under enzyme catalysis. Then, the cross-sectional area of ​​the bridges is gradually expanded by the crystal growth, forming a bridge network between the sand particles. In about 20 minutes, most of the geometric voids are filled, and the structural system shows strong integrity. To further verify the crystal growth process, additional SEM and optical images of the crosslinked network were performed and are shown in Figures 15A-C.

[0089] Crystal growth in ECM is a diffusion-controlled mechanism. The details of the crystal growth process in the sand-gelatin system are represented by a crystal bridge growth model using the diffusion relationship according to Fick's first law. The model was solved analytically to verify the experimental results. The results of the crystal growth modeling framework are presented as the average thickness of the mineral bridges as a function of time in Figure 8. Theoretical equations have been established for crystal growth in beams of square cross section. Here, we consider that calcium carbonate crystals growing on gelatin in the ECM system have the same growth pattern as on polymers. The initial gelatin is considered as a polymer beam, and the volume change of the beam is the result of the subsequent crystal growth.

[0090] Example 17: Self-healing properties To investigate the self-repair and bondability of ECM, it is necessary to simulate the repair process through multiple cycles. For this purpose, an experimental procedure was developed using a three-point bending test. The fracture strength of the beam specimens at each cycle was measured to evaluate the degree of repair in the ECM. For each repair cycle, the fractured samples were placed in a silicon mold and treated with a trace amount of enzyme + calcium solution in the crack surface area (Figure 9A and Figure 9B). Pure CO2 gas was then introduced to the crack surface for 10 min. Mineral precipitation occurred mainly near the wake of the crack in the samples. This process is observable as a liquid film on the surface of the samples in Figure 9C. The repaired samples were then completely dehydrated in an oven and demolded (Figure 9D). The three-point bending fracture test was then performed again. The given steps were repeated for each cycle and the properties of the repaired samples were studied (Figure 9E). In these figures, the mechanical properties of the original sample are referred to as "intact," the first repaired sample is referred to as "1st," the second repaired sample is referred to as "2nd," and so on.

[0091] These results show that the average ultimate load is similar for intact and first cycle samples at about 53N (FIG. 9F). Six samples were tested in each group, and the average maximum load for the first and second cycle samples dropped to 43N. This is a drop of 18.8% from the first to second cycle, a drop of 13.9% from the second to third cycle, and a drop of 35.1% from the third to fourth cycle. After the fourth cycle, the ultimate load tends to stabilize at about 23N, a drop of 52.8% from the intact cycle. These results show that the ECM beams are rebuildable after six damage cycles, demonstrating self-healing properties. These data also support the use of CA and gelatin for the repair of damaged concrete, as shown in further examples herein.

[0092] This method demonstrates the damage and repair process of ECM. In the whole process, only a trace amount of calcium source is required as a filler material. Repaired structural materials with significantly larger defects require the addition of some filler material, which is also required for all other self-repair methods such as MICP and living building materials (LBM). In addition, carbon dioxide from the air can be involved in the self-repair reaction through the catalysis of carbonic anhydrase, so this process also plays a small role in carbon dioxide sequestration during repair. The results in Figure 9F show that the average maximum load decreases with a relatively steady decline from the second repair cycle to the fourth cycle. From the fourth cycle of repair, the average maximum load reaches a plateau at about 23 N, which is half of the intact characteristic. Self-repair is a reconstructed structure of crystalline gelatin on the substrate perpendicular to the crack surface, which can establish effective crystalline bridges, as can be seen in Figure 10. SEM analysis of the samples shows that the main failure mechanism is the destruction of mineral bridges. In the self-repair process, the bridges are re-established after the application of CO2 (Figure 10).

[0093] Here, it is assumed that the entire structural system on the fractured surface after the first fracture is not completely destroyed and the original gelatin-calcium carbonate crystals remain on the surface of the exposed sand grains. From the second repair cycle, the gelatin on the surface of the sand is further dissolved by the aqueous solution, changing the structural integrity at the crack surface. The reason for the stable maximum load after the fourth repair cycle is that the top layer of sand at the fracture surface is exposed without gelatin and these sand particles form cross-links directly to the calcium carbonate crystals. This also clearly demonstrates the efficiency of the method. It is noted that the titration solution penetrates only from one side to the bottom, causing the concentration of gelatin at the lower layer, which then forms a non-uniform crystalline bridge structure with increasing number of repair cycles. The data in Figure 5D and Figure 5E show that the dehydrated gelatin skeleton contributes considerably to the compressive strength of the ECM and therefore its degradation weakens the strength of the sample with increasing number of repair cycles. Furthermore, gelatin aging can also occur during multiple repair cycles.

[0094] Example 18: Enhanced ECM To enhance the physical properties of gelatin, cross-linking agents such as glutaraldehyde, genipin and microbial transglutaminase are applied. Here, glutaraldehyde was chosen as the ECM cross-linking agent, which is by far the most widely used with gelatin due to its availability, low cost and high efficiency in stabilizing collagen materials. Only a very low concentration of glutaraldehyde (1% by weight of gelatin) is sufficient to achieve 100% cross-linking degree and increase the Young's modulus by 20 times with respect to uncross-linked gelatin films. Cross-linking of gelatin with glutaraldehyde involves the reaction of the free amide groups of lysine or hydroxylysine amino acid residues in the polypeptide chain with the aldehyde groups of glutaraldehyde. As the cross-linking degree increases, the thermal and mechanical properties of gelatin also increase. Tannin is used as an additive to improve the mechanical, thermal and moisture absorption behavior of gelatin-based adhesives. It was found that the bond strength (tensile) was increased when tannin was added at 16%. For ECM, the resulting compressive strength of glutaraldehyde was compared to tannin. Figure 11 shows the compressive strength of glutaraldehyde-modified ECM at about 11.5 MPa, which is 28% higher than ECM. On the other hand, tannin modification of ECM samples (27% based on gelatin weight) did not strengthen the ECM structure.

[0095] Although glutaraldehyde is an irritant, thousands of successful bioartificial implants have demonstrated that glutaraldehyde crosslinking is clinically tolerable and has low cytotoxicity at very low concentrations.

[0096] Example 19: Laser-induced hardening of ECM-n To demonstrate the effect of nanoparticles on ECM curing kinetics, 12.5 mm cubes ECM-n (ECM containing 0.1% iron oxide nanoparticles) and ECM were fabricated using the same method and irradiated with the same power laser. Both samples were cured with a 3 W laser (808 nm wavelength) for 12 hours to achieve a certain degree of dehydration in the mass loss evaluation (Figure 28A). As shown in Figure 28B, the maximum surface temperature of ECM-n reaches 110°C at 12 hours to achieve complete dehydration, indicating a stable mass after 9 hours. In contrast, the maximum surface temperature of ECM does not increase, only to 62°C, where the mass loss condition is maintained. The surface temperatures of ECM-n and ECM during the first curing time were recorded in Figures 19A-D. FIG. 19A shows the early curing configuration of a 12.5 mm cube ECM-n in a silicon mold, where the sample was placed under a 3 W continuous wave laser (808 nm) at a distance of 2 cm for 60 min, while the surface temperature on the top and sides was recorded by a thermal camera for 70 min. The maximum surface temperature of the ECM-n sample was observed to increase from 26° C. to 81.5° C. (samples: n=5, median: Med=81.5, standard deviation: SD=3) (FIG. 19B and FIG. 19C). In contrast, the temperature of all ECM samples without nanoparticles never increases above 60° C. (n=5, Med=53, SD=5.7). The temperature distribution is non-uniform, with the highest temperature occurring within the center of the laser beam. From the temperature curves in FIG. 19D, the heating rate of ECM-n is about twice as high in the first 20 min, and both cooling rates are similar, reaching room temperature in 5 and 2 min, respectively, resulting in cooling rates of 11 °C / min (n = 5, SD = 0.82) for ECM-n and 15 °C / min (n = 5, SD = 1.63) for ECM. These data indicate that the addition of nanoparticles does not significantly increase the specific heat capacity of ECM. Due to the low specific heat of nanoparticles, the nanoparticles accelerated the curing by the photothermal effect.

[0097] Example 20: Heat release analysis during initial cure To quantify the early curing kinetics of ECM-n, we used isothermal calorimetry (ITC) to understand the relationship between time and heat flow of ECM-n. In Figure 20, we compared the heat flow in ECM-n samples at 25°C and 60°C. One heat flow peak was detected at two different temperatures in 30 minutes, both peaks appear immediately after injecting the enzyme calcite solution, and the peak at 60°C is more distinct than that at 25°C. The intensity of the peaks increases with temperature, indicating that high temperature significantly enhances the solubility. Higher dissolution of raw materials at higher temperatures provided more scaffolds for the subsequent crosslinking step, thus accelerating the early strength development and final curing of ECM-n samples.

[0098] Example 21: Laser heating of ECM-n at low and room temperatures The application of laser heating on cured ECM-n was also investigated. Figures 21A and 21C show the photothermal effect on cured ECM-n at ambient temperature induced by a 3 W continuous wave laser. Figure 21A shows the experimental setup. Figures 21B and 21C show the top and side views of the temperature contours for an ECM-n sample subjected to laser heating for about 1 h, respectively. For a sample distance of 2 cm from the laser, the peak temperature is concentrated at the center of the sample surface and spreads radially outwards towards the surrounding surface area. The results showed that the maximum temperature of the ECM-n surface increased to 102 °C at room temperature. The effect of thermal convection to the sides can be observed in Figure 3C. The temperature profile shows a layered curve with the lowest temperature at the location furthest from the heat source.

[0099] The photothermal effect of the cured ECM-n was also investigated at low temperatures. The experimental timeline is shown in Figure 21D. The samples were stored in a freezer at -20 °C to ensure a uniform temperature on the surface. The schematic on the left shows the experimental setup. The samples were then irradiated with a 3 W laser in the freezer. Using a thermal camera, the surface temperature was recorded under irradiation for 10 min. At the center of the top surface of the sample, the temperature increased from -20 °C up to 60 °C in 10 min. The above findings provide a new avenue for the application of ECM as a thermally controllable construction material.

[0100] Example 22: Thermal modeling of laser heating To further demonstrate the heat generation capability of ECM-n, computational laser heating was modeled using the finite element method (FEM) and the software package COMSOL Multiphysics 6.5 (COMSOL, Inc. Burlington, MA). Figure 22 shows the maximum temperature as a function of time for an ECM-n sample at three different laser powers. It is observable that the simulation results are slightly lower than the corresponding experimental results, and the normalized temperature profile is proportional to the laser power.

[0101] In the laser heating process of ECM-n, heat transfer occurs via three main mechanisms: conduction, convection, and radiation. The static laser beam obeys Fourier's law of heat conduction. The heat distribution in the ECM-n is then expressed by the following transient heat transfer equation:

number

[0102] Thermal conductivity parameters were used to represent the iron oxide in this ECM-n model for two reasons: 1) during the dehydration process, gelatin undergoes a phase change from a gel to a crystalline state, which complicates the modeling process; and 2) iron oxide has a higher thermal conductivity than sand and gelatin, which significantly affects the temperature of the system.

[0103] The absorption coefficient α depends on the target material and the interaction between the target material and the laser wavelength (808), and most models use a constant absorption coefficient ignoring the effects of the incidence angle and temperature. For simplicity, the absorption coefficient is assumed to be 1, and Q (W / m3) is the laser heat source term. The boundary conditions for Eq. (15) on the side of the ECM-n are heat transfer by convection and on the top surface by radiation. The convection (Newton's law of cooling) in the laser heating process is expressed as follows:

number

[0104] The radiative heat flow rate of an object can be calculated based on the empirical formula of Boltzmann's law below.

number

[0105] Heat convection is always carried by gas or liquid media. Air is the main medium in convection, and for simplicity, the heat convection coefficient is assumed to be uniformly distributed and equal for all surfaces of the boundary, and the natural air heat convection coefficient h is 25 W / m2·k. The emissivity ε of sand is estimated to be 0.95.

[19] σ is the Stefan-Boltzmann constant and n^ is a directional vector. Text and Tamb are the medium air and room temperature, respectively, and both are assumed to be 300 K. For continuous wave laser modes, the fundamental mode of a Gaussian beam is generally preferred, thus providing a Gaussian heat source. The heat generation rate due to a Gaussian profile of transverse model optical intensity of order n can be given as follows: Q(x,y)=pf×f(x,y) (18)

[0106] Here, the laser output intensity (W / m2) is

number

number

[0107] Example 23: Self-repair evaluation under laser hardening This potential feature was demonstrated in a similar series of experiments using nanoparticle-modified ECM (ECM-n) shown in Figures 23A-B. It was observed that the ECM-n cuboid sample autonomously self-repaired upon laser heating without any external force or additional treatment. When fracture occurred, the skeletal crosslinks were exposed at the fracture surface, which means that the mineral crosslinks are weak bonds in the ECM microstructure. The fractured sample was incorporated into a silicon mold, and then CO2 gas was sprayed continuously on the fractured area. In the repair process, it was expected that the precipitated CaCO3 crystals would gradually grow on the skeleton and eventually bridge the fracture interface during laser heating. Additional carbonic anhydrase was added together with calcium solution in the cracked area, which was confirmed to be due to the decrease in enzyme activity during laser light irradiation. When fractured cuboid ECM-n samples were treated with calcium solution containing trace amounts of enzyme (5 μL, 2.9 mg / mL) and compared to samples without enzyme treatment in the calcium source solution, more crystals were observed in the repaired cracks after laser curing (Figures 30A-B). These data also support the use of carbonic anhydrase and gelatin for the repair of cracked concrete.

[0108] Macro-scale characterization of the self-repair process can also be observed from the temperature profile of the sample. The temperature profile contours change during the repair process as expected, as the nanoparticles are carried by the fluid medium and diffuse until the sample is dried. The fracture surface of 4.1 mm × 3.5 mm was completely repaired after 4 h of laser treatment. The resulting ECM-n has the same self-repair ability as ECM and offers potential applications due to its excellent material durability. We also characterized and diagnosed the internal and external microstructure of the crack in the ECMn matrix using micro-computed tomography (μ-CT) scanning (Figure 23B). The μ-CT scan image clearly shows that the crack path disappeared in the three display layers (front, middle, and back), indicating that the internal crack was self-repaired by the laser light irradiation, as expected.

[0109] Example 24: ECM-n morphology and crystallinity characterization Optical and scanning electron microscope (SEM) images of the morphology of ECM and ECM-n at multiple scales were illustrated (Figures 24A-I), showing the variation of calcite crystal size of about 10 μm. Detailed morphological characterization shows that the laser-treated surface and structure of ECM-n are similar to ECM cured in oven without nanoparticles. Calcite crystal distribution and dimensions of hydrogel scaffold were not affected by laser curing. Ordered structures were well assembled in ECM-n and ECM, effectively shielding crack propagation. Sand particles and calcite crystals were randomly assembled within the polymer scaffold, but the overall appearance is similar to body-centered cubic (BCC) crystals. In plan view, sand particles in both samples are connected in at least four directions with crosslinks. Due to the BCC structure type properties, sand slurry material exhibits high ductility during bending tests, with a high strain at 0.0032 compared to normal weight concrete in the range of 0.002-0.003. As a result, localized application of photothermal effect by iron oxide nanoparticles shows moderate effectiveness in ECM-n and high stability and mechanical strength in sand slurry material structure.

[0110] The nanoparticle distribution in ECM-n was also investigated by energy dispersive spectroscopy (EDS), optical microscopy and Raman spectroscopy, as shown in Figures 24B, 24H and 31, respectively. The EDS and optical images clearly show the nanoparticles distributed in each of the sand grains, correlating with the spherical temperature profile. The slight aggregation of nanoparticles occurring on the surface is due to the lack of surfactant during nanoparticle preparation. The surfactant coating consists of various ester-based materials with different levels of chemical complexity depending on the environmental factors, therefore, only physical treatment was applied to the nanoparticles by ultrasonication to avoid adverse effects on the medium.

[0111] To further clarify the distribution of nanoparticles and precipitated crystals, four different positions on the sample surface were spotted by Raman spectroscopy. Raman spectroscopy is a non-destructive analytical technique based on the change in scattering of low energy light from materials and can be used directly on the whole sample. Figure 31 shows the positions on the ECM-n surface corresponding to calcite and γFe2O3. The spectra were processed and plotted proportionally by fitting Gaussian functions. The Raman characteristic peak of calcium carbonate is relatively narrow and shows a high degree of crystallization, and the intensity of the peak is high, indicating a high content of calcite crystals and iron oxide nanoparticles in this region of the sample surface. The above results indicate that the nanoparticle distribution in ECM-n achieves the desired effect. The typical pXRD pattern in Figure 32 shows the presence of precipitated calcium carbonate on ECM-n after laser hardening, where a diffraction peak is observed at 2θ=29.6 degrees, which is consistent with the reference spectrum of calcite. The results verify the crystallinity of the enzyme product as calcite. The morphology is supported by the SEM images in Figures 24A-I.

[0112] Example 25: Mechanical properties of repaired ECM-n Designing high performance construction building materials with superior compressive strength is a long-standing engineering problem. To study the repair performance of the proposed mechanism in laser-induced hardening of ECM and ECM-n, cube-shaped specimens with two types of circular and elliptical defects were fabricated for compression testing. The control and defect samples are shown in (Figures 25A-B). Note that the ECM-n sample was hardened by laser and the defect-free ECM sample was hardened in an oven. The laser-induced repair experiment is shown in (Figure 25A). The normalized values ​​of compressive strength compared to the control are shown in (Figure 25B). The ECM-n sample with a vertical elliptical defect representing a macroscale crack measuring 6 mm in height and 1.5 mm in width and extending to a depth of 12.5 mm throughout the cube sample exhibits approximately 74% of the strength of the undamaged control specimen. A sample with a circular defect that is 2 mm in diameter and extends the entire depth of the 12.5 mm cube sample exhibits approximately 70% of the strength of the undamaged control sample.

[0113] The compressive strength results show that the cube-shaped sample with built-in defects can recover its original compressive strength by adding calcium-enzyme mixed solution to the original sand-gelatin matrix. The material is then bubbled with ultra-pure carbon dioxide for 10 minutes. This is followed by application of the hardening laser for 12 hours. The sample with the large size repaired defect (approximately 6 mm) shows the capability of the proposed method in repairing ECM specimens. It is noted that both repaired defect shape samples are slightly better than the control sample in terms of average compressive strength. The affinity of the existing matrix for the added sand-gelatin repair agent is excellent and the repair process also allows additional hardening of the original matrix, resulting in an overall stiffer structure.

[0114] Comparing the results, the change in strength of the elliptical defect and the repaired elliptical defect ECM-n samples is relatively large. This difference is mainly due to the geometric offset of the elliptical defect during sample preparation in the silicone mold. It should be noted that the samples with prefabricated elliptical and circular defects are destroyed by the initiation of cracks at the defects and growth resulting from the expansion due to the Poisson effect. The p-value of the defective ECM-n samples is less than 0.05, which leads to a significant change in the performance of the structure, while the P-value of the repaired elliptical and circular defect ECM-n is within the statistical error range (>0.05). Thus, the ECM-n with defects maintains mechanical stability after laser repair.

[0115] Example 26: Embedding energy and CO2 of ECM / ECM-n To visualize the impact of ECM / ECM-n on sustainable environmental protection and different types of construction materials, the embodied energy versus embodied CO2 and specific strength versus embodied CO2 associated with different construction materials were compared (Figures 26A and 26B). The Ashby diagram of embodied energy versus embodied strength shows that ECM / ECM-n consumes CO2 compared to other construction materials, as seen by the negative values, since the formation of ECM / ECM-n requires the consumption of carbon dioxide. Furthermore, ECM / ECM-n shows a relatively low energy consumption.

[0116] The boundary considered in this study is cradle-to-gate. Therefore, the energy consumed in the transportation of ECM / ECM-n and the production process are recognized in this report as similar to concrete. The negative CO2 emission and low energy embodiment of ECM / ECM-n is because most of the components can be obtained directly in nature or by simple secondary processing. The enzyme, carbonic anhydrase, added in trace amounts, is isolated from bovine red blood cells or other natural sources, does not produce carbon dioxide and requires little energy. Calcium is available from natural seawater as a by-product of the production of synthetic soda ash. Another low carbon method is to produce calcium from hydrochloric acid and limestone. This process produces hydrogen that can be directly burned or produced by fuel cells to obtain water, which can be achieved with true zero carbon emissions without polluting the environment. Gelatin is extracted by hydrolysis of biological materials in a process that is essentially zero emission. In the method described herein, only 0.1% (based on the weight of sand) of nanoparticles is applied to the medium, which is known to be a clean product capable of capturing and utilizing CO2 from the air. In FIG. 26B, the specific mechanical properties of ECM / ECM-n are also compared with other construction materials. Cracks are assumed to be the initiation of concrete failure. The specific strength of ECM / ECM-n was comparable to the minimum values ​​of LWC (lightweight concrete) and commercial concrete. There is no adverse effect of nanoparticles between ECM and ECM-n, resulting in identical mechanical properties.

[0117] These materials can completely replace lightweight concrete and masonry blocks in all its applications. In particular, ECM-n can be rapidly constructed for temporary foundations, secondary structures and piping even in harsh climates. Here, a guiding flow chart is provided as a reference (Figure 26C). From the above results, the effective area of ​​ECM-n is proportional to the number of nanoparticles and the power of the laser. Therefore, in on-site construction, it is recommended to apply more nanoparticles and higher power laser to ECM-n to ensure the desired effect. For example, to produce a 10ft x 10ft ECM-n slab, it is possible to prepare pre-cured ECM-n on the foundation and then guide 10 industrial laser machines to different spots (assuming the effective area is 0.5ft x 0.5ft). Design a specific time of laser dwell at each spot to achieve complete curing (3W laser guides for 4 hours for a depth of 12.5mm) before moving to the next spot. The total time should be about 160 hours without considering the ambient humidity and natural drying rate, which will decrease exponentially with increasing number of nanoparticles added. However, achieving a balance between time efficiency and power cost is key to this process.

[0118] Example 27: Laser-induced hardening of ECM-n The laser diode corresponds to a heating power of 3 W. The laser beam was transmitted to the tip of a cylindrical probe through a fiber optic cable before propagating to the sample. The distance between the tip of the probe and the sample surface was set at 2 cm to achieve a laser spot size of 1 cm on the sample. The temperature of the heated surface of the sample was recorded by an infrared camera (FLIR One Pro). Then, a 12.5 mm cube sample was heated and dehydrated in a silicon mold for 12 h. A rectangular sample (length 38 mm, depth 8.3 mm, width 4.1 mm and recess length 1.1 mm) was fabricated in the same way. Due to the limited size of the laser beam, the rectangular sample was spot irradiated at three different positions (left, center and right) for 5 h at each point to obtain a fully dehydrated sample.

[0119] Example 28: Laser-induced self-repair of a rectangular sample A one-sided recessed rectangular sample was broken into two pieces. The pieces were assembled and placed into the original mold. 1mL (5μL enzyme, concentration: 2.9mg / mL) of calcium enzyme solution was added to the crack area. Ultra-pure CO2 was introduced onto the surface for 15 minutes to precipitate calcite crystals and form a cross-linked prototype. The sample was then left for another 15 minutes to allow the mineralization solution to naturally penetrate into the interior of the structure. A 3W laser was set 2cm above the sample and performed on the crack for 6 hours, after which the sample could be removed from the mold.

[0120] Example 29: Repair procedure for ECM-n ECM-n was fabricated and cured with oval and circular shaped depressions in a 3D printed silicone mold. After heating with a 3W laser for 12 hours, the sample was removed from the mold and transferred to a cubic silicone mold. The depressions were filled with well-mixed sand-gelatin components, and then the sample was vibrated for 30 seconds. 200 μL of calcium carbonate anhydrous mixed with nanoparticles solution was added to the depression surface, and then aerated with CO2 for 15 minutes. This process should be done slowly enough to ensure that the solution does not penetrate to the bottom and affect the surrounding structure. 3W laser induction was performed on the sample from the same distance on the repaired surface for 12 hours, and finally removed from the mold.

[0121] Example 30: Mineralogical evaluation of precipitates The crystals and nanoparticles in the ECM-n samples were separated from the gelatin and sand matrix for evaluation of the mineral phase in the ECM-n after 12 h of laser induction. The dried crystal and nanoparticle mixture was ground in a mortar and smeared on a sample holder for fingerprint XRD. A Siemens D500 X-ray diffractometer analyzed the samples from 70°2θ using Cu K-α X-ray radiation with a step size of 0.02° and a pressure hold time of 2 s / step. The mineral phase was collected using a data collector. The laser-hardened ECM-n was evaluated using a JEOL JSM-7000F Analytical SEM. First, the samples were sputter-coated with gold powder. Electron dispersive spectroscopy (EDS) was employed to evaluate the nanoparticle distribution in the ECM-n matrix.

[0122] Example 31: Raman spectroscopy A hybrid system (XploRA, HORIBA, France) was used to capture optical images and 100-1200 cm -1 Raman spectra were obtained in the range of 100 nm to 1000 nm. The experiment employed a diode laser (λ = 785 nm) with filter settings of 10% and 100x objective. The acquisition time and accumulation were defined as 5 and 20, respectively.

[0123] Example 32: Heat release analysis during initial cure Isothermal Titration Calorimetry (ITC) can measure the heat output (heat rate) resulting from the hydration reaction of cementitious materials. In addition, ITC tracks the overall reaction rate of the material, providing visibility into hydration behavior that cannot be obtained by simple setting time or compressive strength tests. The time and shape of the heat flow curve obtained by calorimetry indicate the relative performance of the concrete and potential detrimental interactions between the materials used in the mixture.

[0124] Example 33: Laser heating of ECM-n at low and room temperatures All physical and thermal properties of ECM-n samples were extracted from the experimental data for use in FEM. The geometry of ECM-n was modeled with a three-dimensional standard 8-node linear heat transfer element, which is shown in Figure 29A. To develop the multifunctional properties of ECM, the laser thermal mechanism and heating process in ECM-n were investigated and the temperature gradient was simulated assuming that the material properties are not temperature dependent since there is no phase change during the heating process. Figures 29C and 29D show the highest temperature profile located under the laser beam as a function of time, which is consistent with the experimental observations in Figures 21A-C.

[0125] Example 34: ECM-n morphology and crystallinity characterization Raman spectroscopy can provide qualitative analysis of sample phase and morphology, crystallinity, and molecular interactions. Peak profiles are generally defined by three parameters: peak intensity, width, and position. Peak intensity is affected by the concentration and orientation of the object. Peak width relates to crystallinity and homogeneity, and peak position relates to composition. Carbonate phases (calcite) and γFe2O3 comprise the majority of the material and are relatively easy to identify from the phase (~1086 cm-1) and Fe2O3 bands (~225 cm-1) as they both are strong Raman scattering.

[0126] Example 35: Methods and Materials for Repairing Cracks and Fractures As mentioned above, cracks are hypothesized to be the initiation cause of concrete failure. Although very strong, concrete can be brittle and prone to failure. Current repair methods are inadequate and result in weakening of the material.

[0127] The invention described herein, in one embodiment, provides a method for repairing large concrete surfaces using a gelatin-embedded enzyme (carbonic anhydrase) in a calcite solution. This enzyme is found ubiquitously in living systems, for example in humans, where it regulates the pH of intracellular pools and fixes carbon dioxide to produce carbonate, an environmentally useful reaction.

[0128] The repair materials commonly used for concrete cracks mainly include epoxy-based and acrylic resins, which are all environmentally unfriendly and often cause delamination or cracking between the original concrete matrix and the repair material. The crack is the starting point of concrete failure. The present invention provides a method for rapidly repairing large (<5 mm) cracks in concrete. Repair of small cracks and failures of small cement samples soaked in carbonic anhydrase (CA) is described (U.S. Patent No. 10,647,617 issued February 28, 2018). In practical situations where CA repair solutions must be applied to larger cracks on surfaces where soaking and deposition is not practical, the repair solution will run down the material and become diluted, not accelerating the repair. Accelerated repairs can be created and maintained by incorporating CA into a matrix such as silicone beads or into a solvent such as hydrogel or gelatin that does not cause fast diffusion flow in concrete.

[0129] Currently, calcium nitrate is used as a safe, non-toxic corrosion inhibitor (Al-Amoudi, OSB et al. Cement and Concrete Composites 2003, 25 (4), 439-449.) Treatment of concrete with CA before or after hardening not only increases its compressive strength and allows it to self-repair, but also prevents corrosion as shown in the examples herein.

[0130] One aspect of the methods herein relating to concrete repair, corrosion inhibition and self-healing methods is the use of carbonic anhydrase (CA).

[0131] CA is a small protein that flows through concrete and is not retained in the structure. The data in the examples herein show that attaching or embedding CA in gelatin better enables repair and self-healing.

[0132] Thus, the methods provided herein, in one aspect, are used to repair cracks in cementitious surfaces where immersion of the surface is not possible or deposition of the repair solution is not practical. For example, when the concrete surface is vertical and the repair solution flows through the cracks or the repair solution flows through the material and is diluted and does not repair. In the methods provided herein, the enzyme solution of carbonic anhydrase is combined with gelatin used as a scaffold or the enzyme is incorporated into a substrate such as silicone beads. In an alternative embodiment, the carbonic anhydrase is dissolved in an aqueous solvent and embedded in a matrix such as hydrogel, agar, or semi-solid gelatin. Thus, when the enzyme solution is used for application to a cementitious surface, it remains mixed into the cement rather than diffusively flowing down the concrete, allowing the repair reaction to continue for the life of the enzyme activity.

[0133] In various embodiments of the method, the enzyme used (recombinant Bos taurus (bovine) CA-II expressed in Escherichia coli) was purchased from Sigma Aldrich. The enzyme was dissolved in 0.1 M Tris buffer, 160 mM NaCl, pH 9.5, aliquoted and stored at -20°C until use. It is envisaged that one or more carbonic anhydrases from any source are suitable, for example obtained from waste products such as bovine, porcine or ovine blood or offal. Bacterial and yeast enzymes are similarly suitable, obtained from cell mat material by-products of high-value protein fermentation or other industrial sources. It is envisaged that carbonic anhydrases obtained from thermophilic species may be advantageous for use in cement repair in tropical climates, as well as those obtained from xerophilic bacteria in cold climates.

[0134] Enzymes suitable for the methods herein may not be purified or recombinantly produced, for example crude cell extracts precipitated with ammonium sulfate to 60% to 65% saturation or extracted with organic solvents and redissolved may be sufficient for large scale industrial concrete use. Methods for purification of carbonic anhydrase are well known, see for example da Costa et al., Chemosphere 88 (2012) 255-259.

[0135] In the examples shown in Figures 33 and 34A and 34B herein, recombinant bovine enzyme product was precipitated from a 5 μL aliquot of 49.6:49.6:0.74:0.0001 volume percent four-component solution of 20 mM bovine CA provided in 200 mL of 2 M calcium chloride dihydrate, 200 mL of 0.1 M Tris base, ultrapure water, and 150 mM sodium chloride in a beaker on a stir plate. The amount of carbonic anhydrase (CA) used is very small and is recycled through multiple preparations as a catalyst. The primary 50:50 percent solution of 2 M CaCl2 and 0.1 M Tris base had an initial pH of 9.5. With the addition of CO2 gas by bubbling, the pH was observed to drop by 0.1 units as a result of enzyme activity. A 5 μL aliquot of CA solution was rinsed from its container with 3 mL of ultrapure water and added to the beaker. Upon continuous bubbling of CO2 gas over a period of 20 minutes, the pH of the solution was observed to decrease from 9.5 to 7.4.

[0136] The CA solution was allowed to stand for 24 hours and then the supernatant was removed. The CA solution was thoroughly stirred for 2 minutes and 20 mL of the solution was siphoned off and heated to 35°C. Gelatin (Knox, 1 g) was mixed with 20 mL of the solution for 2 minutes and the solution was continuously stirred until the gelatin was dissolved and a 5% gelatin solution was obtained. The concrete slab was placed on two platforms so that the depression was floating. A volume of 10 mL of the CA solution containing gelatin was evenly filled into the depression and the depression was completely covered with the solution. The concrete slab and depression were allowed to air dry for 24 hours. The depression was reapplied with 10 mL of the CA solution containing gelatin. After air drying for 24 hours, the depression was filled with 7 mL of the CA solution without gelatin. The slab and depression were allowed to air dry for 4 hours and the depression was refilled with 7 mL of the CA solution without gelatin. The procedure of air drying for 4 hours and reapplication of the CA solution without gelatin was repeated for 5 days. The CA solution with gelatin maintained the seal and the CA solution without gelatin remained in the pits. After thorough air drying, pits of various sizes were observed to be repaired after 7 and 14 days, respectively, as shown in Figures 33, 34A, and 3B.

[0137] Further provided herein is a method for preventing corrosion of concrete and materials involving a concrete corrosion inhibitor admixture using carbonic anhydrase to reduce chloride penetration in concrete as demonstrated by the data presented in the figures herein. A major factor in extending the life of concrete structures is the use of corrosion inhibitors. The global corrosion inhibitors market is expected to grow at a CAGR of 3.54% from USD 7.7 billion in 2020 to USD 10.09 billion in 2028. The enzyme-based corrosion inhibitors provided herein improve the durability of concrete structures by significantly reducing the porosity of concrete during hardening.

[0138] The resulting reduced porosity of the concrete blocks the access of harmful ions such as chloride ions, thus extending the life of the concrete structure. Chloride ions are harmful to concrete and are the main cause of concrete failure in coastal areas. Porosity is evaluated by physical analysis methods shown in the drawings herein. In practical use during construction, the use of visible dyes also allows for quicker and easier determination of porosity in the field to assess the reduced porosity and the resulting improved corrosion resistance. Preferably, negatively charged dyes are used that mimic chloride ions in size and charge. Coomassie Blue or Brilliant Blue, which have a negative charge at neutral pH, are exemplary dyes for this purpose. See also Savicheva, E. et al. Angewandt. Chem. Int. Ed. Engl (2020) 59 (14): 5505-5509.

[0139] Globally, concrete is a trillion dollar industry. The inexpensive additives provided herein, as corrosion inhibitors, significantly extend the life of concrete structures such as buildings, roads, pavements, etc. All current corrosion inhibitors adversely affect the plasticity and strength of concrete. Three sets of experimental results independently show that the enzymatic corrosion inhibitor methods and materials herein have superior performance compared to all current corrosion inhibitors on the market while having no adverse effect on the mechanical properties of concrete.

[0140] Nearly all current corrosion inhibitors on the market are calcium nitride based. Calcium nitride can be used as a corrosion inhibitor to reduce the porosity of concrete, but it has a detrimental effect on the mechanical properties of concrete, such as strength. The data herein show that the enzyme-based method has no detrimental effect on concrete.

[0141] Nearly all current corrosion inhibitors on the market are calcium nitride based. Calcium nitride can be used as a corrosion inhibitor to reduce the porosity of concrete, but has a detrimental effect on the mechanical properties of concrete, such as strength. The enzyme-based method provided herein does not have any detrimental effect on concrete, in contrast, the enzyme-based method and materials are self-healing.

[0142] Various configurations exhibiting the above features and advantages disclosed herein are further pointed out and described in the claims and examples, the contents of all cited references are incorporated herein in their entirety.

Claims

1. 1. A method for repairing at least one crack or pit in a cementitious surface, comprising: treating the at least one crack or pit in the cementitious surface with at least one carbonic anhydrase preparation, the preparation containing carbonic anhydrase non-covalently immobilized on a granular substrate or embedded in a semi-solid bead matrix; subjecting the cementitious treated surface to ambient conditions of atmospheric carbon dioxide and temperature, thereby repairing the at least one crack. The method includes:

2. 2. The method of claim 1, further comprising repeating the treatment of the at least one crack or pit with the carbonic anhydrase preparation and subjecting the treated surface to the ambient conditions.

3. 3. The method of claim 2, further comprising allowing the contacted and treated cementitious surface to air dry before repeating the treatment.

4. 2. The method of claim 1, wherein the carbonic anhydrase preparation further comprises at least one component selected from native carbonic anhydrase, calcium ions, a buffer, and water.

5. 2. The method of claim 1, wherein the granular substrate of the carbonic anhydrase preparation is at least one selected from silicone beads, silica gel, silicon dioxide, disiloxane, silicic acid, silanols, organosilicon compounds, sand, grit, cellulose and cellulose derivatives.

6. 2. The method of claim 1, wherein the semi-solid bead matrix of the carbonic anhydrase preparation is prepared from at least one selected from hydrogel, agar, and gelatin.

7. 2. The method of claim 1, wherein the carbonic anhydrase is recombinantly produced.

8. 2. The method of claim 1, wherein the carbonic anhydrase is purified or partially purified from a biological source, e.g., a mammalian enzyme by-product of the meat industry, e.g., produced from bovine blood, or a bacterial or yeast enzyme by-product of antibiotic or high value protein fermentation.

9. 9. The method of claim 8, wherein the bacterial enzyme is from a thermophilic or xerophilic species.

10. 1. A method for improving the durability and corrosion resistance of a cementitious surface, comprising: contacting the pre-hardened cement mixture with at least one carbonic anhydrase (CA) preparation to form an enzyme-cement mixture (ECM); applying said ECM to a surface and subjecting said mixture on said surface to ambient atmosphere to harden, removing a core cylindrical sample, and observing increased crystallization or decreased uptake of a visible dye, preferably negatively charged to mimic chloride ions, in said sample after a period of at least 2 days to at least 7 days, thereby reducing porosity and imparting corrosion resistance in the resulting CA-contacted cementitious surface as compared to a control cement not contacted with CA. The method includes:

11. 11. The method of claim 10, wherein the carbonic anhydrase preparation comprises CA non-covalently immobilized on a particulate substrate selected from silicone beads, silica gel, sand, grit, cellulose and cellulose derivatives, or the carbonic anhydrase preparation comprises CA embedded in a semi-solid bead matrix comprising a hydrogel or gelatin.

12. 11. The method of claim 10, wherein reducing the porosity of the resulting CA-contacted cementitious surface further comprises reducing the permeability of the surface to harmful environmental corrosive agents.

13. 11. The method of claim 10, wherein reducing the porosity of the resulting cementitious surface comprises reducing the penetration of harmful salt ions, including chloride salts.

14. 11. The method of claim 10, wherein the CA is selected from at least one of: recombinantly produced, purified from food industry by-products, partially purified from food industry by-products, purified from fermentation by-products, and partially purified from fermentation by-products.

15. Applying the ECM ++ The method of claim 10 further comprising adding ions to the surface.

16. The Ca ++ The method of claim 15, wherein is calcium formate.

17. The contacting of the cement includes contacting the Ca ++ The method of claim 10 further comprising adding ions to the mixture.

18. 1. An erosion resistant cementitious mixture having improved durability comprising carbonic anhydrase in an aqueous solution in a granular admixture, the enzyme being associated with at least one selected from silicone beads, silica gel, sand, grit, cellulose, and cellulose derivatives at a pH of 4.5 to 9.

5.

19. 20. The corrosion resistant cement mixture of claim 18, wherein the enzyme is present in a concentration range selected from the group consisting of 100 nM to 500 nM, 500 nM to 1 μM, 1 μM to 5 μM, and 5 μM to 10 μM.

20. Ca ++ 20. The corrosion resistant cementitious mixture of claim 18, further comprising: